Iron-manganese modified chitosan composite material, and preparation method and application thereof

CN122916274APending Publication Date: 2026-10-16HUNAN AGRI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611416526.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-14
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0010]本发明的目的在于提供一种铁锰改性壳聚糖复合材料及其制备方法和应用,以解决基础铁锰改性壳聚糖复合材料中锰氧化位点的形成量和形成位置不易控制,以及Sb(III)氧化过程与不同价态锑固定过程衔接不足的问题

Benefits of technology

本发明通过碱性共沉淀将铁氧羟化物和第一锰氧化物负载于壳聚糖基体。壳聚糖分子链中的氨基和羟基可以参与铁、锰物种的配位和固定,为铁氧羟化物和第一锰氧化物提供负载骨架,减少铁锰无机颗粒之间的直接聚集,并保留壳聚糖基体中的表面官能团。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916274A_ABST
    Figure CN122916274A_ABST
Patent Text Reader

Abstract

The present application relates to the field of high polymer composite adsorption material and environmental pollution treatment technology, and discloses a kind of iron manganese modified chitosan composite material and its preparation method and application.The composite material includes chitosan matrix and the iron oxyhydroxide, first manganese oxide and second manganese oxide loaded on it, and the side group containing quaternary ammonium cation grafted on it.Preparation, trivalent iron salt, divalent manganese salt and chitosan are co-precipitated to obtain a basic composite;Mn 2+ It is adsorbed according to the amount of 2 / 3 of Mn 2+ Potassium permanganate is added, and secondary manganese mineralization is carried out at pH 8.0±0.2;The obtained composite is dispersed in water, and 0.030-0.122 g of glycidyltrimethylammonium chloride active ingredient is added per 1.00 g of dry base composite, and the reaction is carried out at pH 8.1-8.5 to obtain the composite material.The composite material is used for antimony-containing water treatment and antimony-contaminated soil remediation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer composite adsorption materials and environmental pollution control technology, specifically relating to an iron-manganese modified chitosan composite material, its preparation method, and its application. Background Technology

[0002] Inorganic antimony in environmental media mainly exists in trivalent and pentavalent forms. In weakly acidic, neutral, and weakly alkaline water bodies, Sb(III) mainly exists as electrically neutral Sb(OH)3, and Sb(V) mainly exists as Sb(OH)6. - Antimony exists in anionic form. The two valence states of antimony have different charge states and surface reaction characteristics. The surface composition, redox activity, and charge properties of the material all affect the antimony removal process.

[0003] Iron oxides and ferrooxide hydroxylates contain Fe-OH groups on their surfaces, which can adsorb Sb(III) and Sb(V) through surface complexation and other mechanisms. Manganese oxides exhibit redox activity, promoting the conversion of Sb(III) to Sb(V), and the valence and dissolution states of the manganese component also change during the reaction. Combining iron and manganese components can simultaneously provide oxidation and adsorption sites for antimony. This technical approach has been applied to antimony-containing water treatment and antimony-contaminated soil stabilization research.

[0004] When iron-manganese oxide particles are small, they tend to aggregate, causing some surface-active sites to be blocked by adjacent particles. Chitosan molecules contain amino and hydroxyl groups, which can coordinate with iron and manganese ions and provide a carrier for the deposition of iron-manganese oxides. Loading iron-manganese oxides onto a chitosan matrix can restrict the independent aggregation of inorganic particles and introduce chitosan's own coordination sites into the composite material. However, chitosan loading cannot directly determine the phase composition, manganese valence state, and surface distribution of the iron-manganese components.

[0005] Publicly available research has reported composite materials of chitosan and iron / manganese oxides, as well as methods for loading iron / manganese oxides onto chitosan or other amino-containing supports. Some of these materials have already been used for the adsorption and treatment of Sb(III), Sb(V), or other heavy metal pollutants. Therefore, simply combining iron oxides, manganese oxides, and chitosan, or routinely adjusting the ratio of iron salts to manganese salts, is unlikely to provide a clear distinction from existing technologies.

[0006] When using Fe(III) and Mn(II) salts for alkaline coprecipitation, the Fe / Mn molar ratio reflects the raw material composition and cannot directly represent the manganese valence state, number of effective oxidation sites, and spatial distribution in the resulting material. The manganese-containing precipitate formed by Mn(II) under alkaline conditions is also affected by dissolved oxygen, pH, temperature, reaction time, and the surface state of the support. Even with the same feed ratio, the manganese phase and valence state composition of the materials obtained under different preparation conditions may still differ, causing fluctuations in the Sb(III) oxidation performance of the materials.

[0007] Permanganate can further oxidize manganese-containing precursors to form manganese oxides with higher valence states. However, if the amount of permanganate added and the reaction site are not controlled, the manganese oxidation reaction may occur simultaneously on the support surface and in the liquid phase, forming manganese oxide particles that are weakly bound to the support. The newly formed manganese oxides may also cover part of the ferrooxyhydroxylate surface, reducing the accessible Fe-OH groups. When the amount of permanganate added is too large, there is also the possibility of oxidizing the amino, hydroxyl, or sugar ring structures of chitosan, thereby changing the composition and pore structure of the composite material.

[0008] After Sb(III) is oxidized to form Sb(V), it mainly exists in the anionic form. The adsorption of Sb(V) by ferrooxyhydroxylates is affected by solution pH, surface charge, and coexisting anions such as phosphate and sulfate. Simply increasing the manganese content may increase oxidation sites, but it may also reduce the accessibility of the iron component surface. Therefore, the overall fixation capacity of a material for antimony in different valence states cannot be judged solely based on the manganese content.

[0009] Therefore, chitosan-supported iron-manganese oxide materials still need to address the problem of controlling the amount and location of the second manganese oxide formation, and coordinate the Sb(III) oxidation and Sb(III) and Sb(V) fixation processes while retaining the hydroxyl groups on the surface of the iron oxide hydroxylate and the structure of the chitosan matrix. Summary of the Invention

[0010] The purpose of this invention is to provide an iron-manganese modified chitosan composite material, its preparation method and application, in order to solve the problems that the formation amount and formation position of manganese oxidation sites in the basic iron-manganese modified chitosan composite material are not easy to control, and that the connection between the Sb(III) oxidation process and the antimony fixation process of different valence states is insufficient.

[0011] To achieve the above objectives, according to one aspect of the present invention, an iron-manganese modified chitosan composite material is provided, comprising a chitosan matrix, an iron oxide hydroxyl group supported on the chitosan matrix, a first manganese oxide and a second manganese oxide, and a side group containing a quaternary ammonium cation grafted onto the chitosan matrix.

[0012] The ferric oxide hydroxylate and the first manganese oxide are formed by co-precipitation of trivalent ferric salt, divalent manganese salt, and chitosan under alkaline conditions, with a Fe / Mn molar ratio of 3:1 for the trivalent ferric salt and divalent manganese salt. The second manganese oxide is formed by pre-adsorbing Mn onto the surface of a chitosan matrix containing the ferric oxide hydroxylate and the first manganese oxide. 2+ It is formed by reacting with permanganate. The side group containing the quaternary ammonium cation is formed by the ring-opening reaction of the epoxy group of glycidyltrimethylammonium chloride with some of the amino groups in the chitosan matrix.

[0013] In this invention, neither the first manganese oxide nor the second manganese oxide is limited in specific crystal form, average manganese valence state, or stoichiometric ratio. The second manganese oxide can be generally represented as Mn. x O y x and y represent the compositional relationship between manganese and oxygen in the obtained second manganese oxide, and do not indicate that x and y have predetermined values.

[0014] Preferably, the ferric oxide hydroxylate is formed by hydrolysis and condensation of ferric salt under alkaline conditions, and the first manganese oxide is formed by alkaline co-precipitation and aging of divalent manganese salt.

[0015] Preferably, the side group of the quaternary ammonium cation is 2-hydroxy-3-trimethylammoniumpropyl, and the counter ion of the quaternary ammonium cation is chloride ion.

[0016] Preferably, the iron oxide hydroxylate and the first manganese oxide are formed by co-precipitation of 5.0 g chitosan with 14.61 g FeCl3·6H2O and 3.58 g MnCl2·4H2O.

[0017] According to another aspect of the present invention, a method for preparing the iron-manganese modified chitosan composite material is provided, comprising the following steps: S1. Chitosan is dissolved in hydrochloric acid solution to obtain chitosan solution; ferric salt and divalent manganese salt are dissolved in water at a Fe / Mn molar ratio of 3:1 to obtain ferric-manganese salt solution.

[0018] S2, the iron-manganese salt solution is added to the chitosan solution, sodium hydroxide solution is added, the pH value of the reaction system is adjusted to 8.5-9.0, a co-precipitation reaction is carried out, and after aging, solid-liquid separation, washing, drying and pulverization, the basic iron-manganese modified chitosan complex is obtained.

[0019] S3, the basic iron-manganese modified chitosan complex is dispersed in an aqueous MnCl2 solution, so that Mn 2+ The Mn adsorbed on the surface of the basic iron-manganese modified chitosan complex was subjected to solid-liquid separation and washing after contact, and the amount of Mn adsorbed on the basic iron-manganese modified chitosan complex was measured. 2+ The amount of substance.

[0020] S4, Disperse the solid obtained in step S3 in water, add potassium permanganate, wherein the amount of potassium permanganate is equal to the amount of Mn adsorbed by the basic iron-manganese modified chitosan complex in step S3. 2+ Two-thirds of the amount of substance. During the addition of potassium permanganate, the pH of the reaction system was maintained at 8.0±0.2 using sodium hydroxide solution. After reaction, solid-liquid separation and washing, a secondary manganese mineralization complex was obtained.

[0021] S5, according to the ratio of 0.030 to 0.122 g glycidyltrimethylammonium chloride active ingredient added per 1.00 g dry basis secondary manganese mineralization complex, the secondary manganese mineralization complex is dispersed in water, glycidyltrimethylammonium chloride is added, the pH value of the reaction system is adjusted to 8.3±0.2 and the reaction is carried out. After solid-liquid separation, washing and drying, the iron-manganese modified chitosan composite material is obtained.

[0022] Preferably, in step S1, 5.0 g of chitosan is added to 300 mL of 0.1 mol / L hydrochloric acid solution and stirred at 30°C and 350 r / min until dissolved; 14.61 g of FeCl3·6H2O and 3.58 g of MnCl2·4H2O are added to 300 mL of water and stirred for 30 min to obtain the iron-manganese salt solution.

[0023] Preferably, in step S2, the iron-manganese salt solution is added to the chitosan solution at a rate of 5 mL / min; 1 mol / L sodium hydroxide solution is added to adjust the pH of the reaction system to 8.5-9.0, and the reaction is carried out at 45℃ and 350 r / min for 3 h. After cooling to room temperature, the mixture is aged for 12 h, the solid and liquid are separated, and the mixture is washed with water until the pH of the washing solution is 7.0. The mixture is then vacuum dried at 60℃ for 12 h, pulverized, and passed through a 100-mesh sieve.

[0024] Preferably, in step S3, 5.00 g of the basic iron-manganese modified chitosan complex is dispersed in 500 mL of Mn 2+ The pH of the reaction system was adjusted to 7.0±0.2 in a 5.00 mmol / L MnCl2 aqueous solution, and the reaction was carried out at 25℃ and 300 r / min for 2 h. After the reaction was completed, solid-liquid separation was performed, and the resulting solid was washed with water 3 times, with 100 mL of water used each time.

[0025] The Mn adsorbed by the basic iron-manganese modified chitosan complex 2+ The amount of substance is determined by the following formula: ; In the formula, Mn retained in the basic iron-manganese modified chitosan complex after washing 2+ Amount of substance, measured in mol; Mn in the MnCl2 aqueous solution before contact 2+ The molar concentration, expressed in mol / L; Mn in the liquid phase after contact 2+ The molar concentration, expressed in mol / L; The volume of the MnCl2 aqueous solution is expressed in liters (L). Mn washed off from the resulting solid during the washing process 2+ Amount of substance, measured in mol; Preferably, in step S4, 0.80 mmol of potassium permanganate is added in the form of 80.0 mL of an aqueous solution with a concentration of 0.010 mol / L over 30 min; after the addition is completed, the reaction is carried out at 25 °C and 300 r / min for 2 h.

[0026] Preferably, in step S5, the secondary manganese mineralization complex is dispersed in water at a ratio of 50 mL of water per 1.00 g of dry-based secondary manganese mineralization complex.

[0027] Preferably, in step S5, the pH of the reaction system is adjusted to 8.3±0.2 using a 0.1 mol / L sodium hydroxide solution, and the glycidyltrimethylammonium chloride is added. The amount of the effective component of the glycidyltrimethylammonium chloride added is 0.030 to 0.122 g per 1.00 g dry basis secondary manganese mineralization complex. During the addition process, the pH of the reaction system is maintained at 8.1 to 8.5.

[0028] Preferably, in step S5, after the addition of glycidyltrimethylammonium chloride, the reaction is carried out at 60°C and 300 r / min for 15 h; the solid obtained from the reaction is washed with water 5 times, each time using 20 mL of water per 1.00 g dry basis secondary manganese mineralization complex, and the washed solid is vacuum dried at 60°C for 12 h, pulverized and passed through a 100 mesh sieve.

[0029] According to another aspect of the invention, the application of the iron-manganese modified chitosan composite material in the treatment of antimony-containing water is provided.

[0030] Compared with the prior art, the beneficial effects of the present invention are: This invention loads ferrooxyhydroxylates and a first manganese oxide onto a chitosan matrix via alkaline co-precipitation. The amino and hydroxyl groups in the chitosan molecular chain can participate in the coordination and fixation of iron and manganese species, providing a loading framework for the ferrooxyhydroxylates and the first manganese oxide, reducing direct aggregation between iron and manganese inorganic particles, and retaining the surface functional groups in the chitosan matrix.

[0031] This invention first makes Mn 2+ Adsorbed onto the surface of the basic iron-manganese modified chitosan complex, the unadsorbed Mn is separated by solid-liquid separation and washed away. 2+ Then, based on the adsorption of Mn 2+ The amount of potassium permanganate added is determined by the amount of substance. Pre-adsorbed Mn 2+ This provides a surface anchoring site for subsequent reactions, allowing the second manganese oxide to preferentially form on the surface of the basic iron-manganese modified chitosan complex. According to Mn... 2+ Controlling the amount of potassium permanganate fed by adsorption capacity can reduce the non-directional oxidation that occurs when potassium permanganate has no corresponding reactant, and reduce the possibility of free manganese oxides forming in the liquid phase and newly formed manganese oxides continuously covering the surface of ferrooxyhydroxylates.

[0032] This invention controls the amount of glycidyltrimethylammonium chloride added according to the dry basis weight of the secondary manganese mineralization complex, and maintains the pH of the reaction system at 8.1–8.5. This pH condition increases the proportion of chitosan amino groups in their unprotonated form, allowing the amino groups to undergo nucleophilic attack on the epoxy groups of glycidyltrimethylammonium chloride and undergo a ring-opening reaction, forming side groups containing quaternary ammonium cations on the chitosan matrix. This feeding method is independent of the accessible amino group determination results and allows direct control of the reactant dosage for different batches based on the dry basis weight of the secondary manganese mineralization complex.

[0033] Side groups containing quaternary ammonium cations introduce fixed positive charge sites in composite materials. Sb(V) in neutral water primarily exists as Sb(OH)6. - The presence of anionic antimony species, with their fixed positive charge positions, facilitates the enrichment of anionic antimony species at the material interface; the hydroxyl groups on the surface of the ferrooxyhydroxylide can form surface complexes with antimony species. The second manganese oxide, the side groups containing quaternary ammonium cations, and the ferrooxyhydroxylide are jointly loaded or grafted onto the chitosan matrix, providing structural conditions for the contact between Sb(III) and manganese oxide sites, the enrichment of anionic antimony species at the material interface, and the binding of antimony species to the surface of the ferrooxyhydroxylide.

[0034] This invention will use Mn 2+ The process combines pre-adsorption, secondary manganese mineralization with a limited feed amount, and partial cationization of chitosan in sequence. This increases manganese oxidation sites and fixes positive charge positions while retaining the ferrohydroxyl component in the basic complex. The preparation process mainly employs an aqueous phase reaction and is vacuum dried at 60°C, eliminating the need for high-temperature calcination. Attached Figure Description

[0035] Figure 1 This is a scanning electron microscope image of the original iron-manganese modified chitosan composite material prepared in Comparative Example 1.

[0036] Figure 2The image shows the X-ray diffraction pattern of the original iron-manganese modified chitosan composite material prepared in Comparative Example 1.

[0037] Figure 3 The nitrogen adsorption-desorption isotherm and pore size distribution of the original iron-manganese modified chitosan composite material prepared in Comparative Example 1 are shown.

[0038] Figure 4 The Fourier transform infrared spectrum of the original iron-manganese modified chitosan composite material prepared in Comparative Example 1 is shown.

[0039] Figure 5 The figure shows the pseudo-first-order and pseudo-second-order adsorption kinetics of Sb(III) and Sb(V) on the original iron-manganese modified chitosan composite material prepared in Comparative Example 1.

[0040] Figure 6 The Langmuir and Freundlich isotherm fitting curves of Sb(III) and Sb(V) for the original iron-manganese modified chitosan composite material prepared in Comparative Example 1 are shown.

[0041] Figure 7 The figure shows the results of five adsorption-desorption cycles of Sb(III) and Sb(V) on the original iron-manganese modified chitosan composite material prepared in Comparative Example 1. Figure 7 (a) shows the results of five adsorption-desorption cycles of Sb(III). Figure 7 (b) shows the results of five adsorption-desorption cycles of Sb(V).

[0042] Figure 8 The graph shows the changes in extractable antimony and passivation rate after treating antimony-contaminated soil with different dosages of the material. Figure 8 (a) shows the curves of the change in the content of extractable antimony in the soil with the incubation time under different material addition amounts. Figure 8 (b) is a graph showing the antimony passivation rate in the soil after 35 days of cultivation.

[0043] Figure 9 Scanning electron microscope images and surface distribution maps of iron and manganese elements are shown for the materials prepared in Comparative Examples 1, 3, 4, and 1. Figure 9 (a)-(d) are the characterization results of the material prepared in Comparative Example 1. Figure 9 (e)-(h) represent the characterization results of the materials prepared in the comparative example. Figure 9 (i)-(l) are the characterization results of the materials prepared in Comparative Example 4. Figure 9 (m)-(p) represent the characterization results of the material prepared in Example 1; Figure 9 (a), (e), (i), and (m) are scanning electron microscope images. Figure 9 (b), (f), (j), and (n) are surface distribution diagrams of iron element. Figure 9 (c), (g), (k), and (o) are surface distribution diagrams of manganese. Figure 9 (d), (h), (l), and (p) are superimposed diagrams of iron and manganese elements.

[0044] Figure 10 shows a comparison of X-ray diffraction patterns of the materials prepared in Comparative Example 1, Comparative Example 3, and Example 1.

[0045] Figure 11 shows the X-ray photoelectron spectroscopy characterization of the materials prepared in Comparative Example 1 and Example 1, where Figure 11(a) is the full XPS spectrum, Figure 11(b) is the N1s peak fitting spectrum of Comparative Example 1, Figure 11(c) is the N1s peak fitting spectrum of Example 1, and Figure 11(d) is the Cl2p spectrum of Comparative Example 1 and Example 1.

[0046] Figure 12 shows a comparison of the antimony removal performance in water and the soil passivation results of the materials prepared in each embodiment and comparative example. Figure 12(a) shows the equilibrium adsorption amount of Sb(III) by the materials prepared in Examples 1 to 3 and Comparative Examples 1 to 5. Figure 12(b) shows the equilibrium adsorption amount of Sb(V) by the materials prepared in Examples 1 to 3 and Comparative Examples 1 to 5. Figure 12(c) shows the extractable antimony content and passivation rate of the soil after 35 days of cultivation in the blank group, the treatment group of Comparative Example 1, and the treatment group of Example 1. Detailed Implementation

[0047] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are preferred embodiments of the present invention and should not be considered as excluding other embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0048] In the claims and description of this invention, the terms "comprising," "having," and variations thereof are used to mean "including but not limited to."

[0049] The iron-manganese modified chitosan composite material of the present invention uses chitosan as an organic matrix and includes an iron oxide hydroxylide, a first manganese oxide, and a second manganese oxide loaded on the chitosan matrix, as well as side groups containing quaternary ammonium cations grafted onto the chitosan matrix. The iron oxide hydroxylide and the first manganese oxide are formed by alkaline co-precipitation, and the second manganese oxide is formed by Mn pre-adsorbed on the surface of the base composite. 2+ It reacts with permanganate to form a side group containing quaternary ammonium cation, which is formed by the ring-opening reaction of the epoxy group of glycidyltrimethylammonium chloride with some of the amino groups in chitosan.

[0050] In this invention, neither the first manganese oxide nor the second manganese oxide is limited in specific crystal form, average manganese valence state, or stoichiometric ratio. The second manganese oxide can be generally represented as Mn. x O y x and y represent the compositional relationship between manganese and oxygen elements in the obtained manganese oxide, and do not imply that x and y have predetermined values. The first manganese oxide and the second manganese oxide are distinguished according to their formation stage and formation mode, not by their specific chemical formula.

[0051] To prepare the chitosan solution, 5.0 g of chitosan was added to 300 mL of a 0.1 mol / L hydrochloric acid solution. The solution was stirred at 30 °C and 350 r / min until the chitosan dissolved, yielding the chitosan solution. The hydrochloric acid protonated some of the amino groups in the chitosan, weakening the hydrogen bonds between the chitosan molecular chains and dispersing the chitosan in the aqueous phase. Using the above-mentioned hydrochloric acid concentration and volume allows for control of the acid content in the system while providing an acidic dissolution environment, facilitating subsequent pH adjustment with sodium hydroxide.

[0052] 14.61 g of FeCl3·6H2O and 3.58 g of MnCl2·4H2O were added to 300 mL of water and stirred for 30 min to dissolve the two metal salts, yielding an iron-manganese salt solution. Based on the above feed amounts, the molar ratio of Fe to Mn is 3:1. During the preparation of the iron-manganese salt solution, the pH should be maintained at an acidic level or close to the pH level formed by the hydrolysis of the metal salts themselves. Alkali solution should not be added before adding the chitosan solution to reduce the amount of Fe... 3+ Pre-hydrolysis forms a precipitate that separates from chitosan.

[0053] The chitosan solution was placed at 45℃ and stirred at 350 r / min. The iron-manganese salt solution was added to the chitosan solution at a rate of 5 mL / min. Controlling the addition rate of the iron-manganese salt solution can reduce abrupt changes in local metal ion concentration, thus preventing Fe... 3+ and Mn 2+ It comes into contact with the amino and hydroxyl groups in the chitosan molecular chain before alkaline precipitation.

[0054] After the iron-manganese salt solution was added, a 1 mol / L sodium hydroxide solution was slowly added to adjust the pH of the reaction system to 8.5–9.0. As the pH increased, the protonated amino groups in chitosan gradually deprotonated, and the chitosan changed from a dissolved state to an insoluble matrix. 3+ Under alkaline conditions, it undergoes hydrolysis and condensation to form ferrooxyhydroxylates; Mn 2+Hydrolysis, precipitation, and the formation of the first manganese oxide during the reaction and aging process occur. The amino and hydroxyl groups in chitosan, as well as the surface of the already formed inorganic particles, provide attachment sites for subsequent precipitation, allowing the ferrooxyhydroxylates and the first manganese oxide to be loaded onto the chitosan matrix.

[0055] The coprecipitation reaction was carried out at 45℃ and 350 r / min for 3 h. The pH of the system was continuously monitored during the reaction, and 1 mol / L sodium hydroxide solution was added to maintain the pH value between 8.5 and 9.0, reducing Fe. 3+ The pH fluctuations caused by the consumption of alkali during hydrolysis and precipitation are due to the process. The manganese oxide formed in this stage is called the first manganese oxide, and is not limited to MnO2 based on the feeding conditions.

[0056] After the coprecipitation reaction was completed, the reaction system was cooled to room temperature and allowed to stand for 12 h for aging. During the aging process, the primary iron-manganese precipitate continued to undergo dehydration, condensation, and structural adjustment, and the contact between the inorganic components and the chitosan matrix tended to stabilize. After aging, solid-liquid separation was performed, and the obtained solid was washed with water until the pH of the washing solution reached 7.0 to remove soluble chloride salts, sodium salts, and unloaded metal ions. The washed solid was vacuum dried at 60 °C for 12 h, pulverized, and passed through a 100-mesh sieve to obtain the basic iron-manganese modified chitosan complex.

[0057] Weigh 5.00 g of the basic iron-manganese modified chitosan complex and disperse it in 500 mL of Mn 2+ The solution was prepared in a 5.00 mmol / L MnCl2 aqueous solution. The pH of the system was adjusted to 7.0 ± 0.2, and the mixture was contacted at 25 °C and 300 r / min for 2 h to allow the MnCl2 to react with the solution. 2+ It comes into contact with the ferrooxy hydroxyl group, the first manganese oxide and the chitosan functional group on the surface of the base complex, and is adsorbed on the surface of the base complex and in the accessible pores.

[0058] After contact, solid-liquid separation was performed, and the liquid phase after contact was collected. The resulting solid was washed three times with water, 100 mL each time, and all washing liquid was collected. The Mn content in the MnCl2 aqueous solution before contact was determined. 2+ Concentration of Mn in the liquid phase after contact 2+ Concentration and total Mn content in the washing solution 2+ Content. Mn 2+ Concentration was determined by inductively coupled plasma atomic emission spectrometry (ICP-AES), or by elemental analysis methods that have been validated to meet the requirements for detection limits and precision.

[0059] Mn adsorbed by the basic iron-manganese modified chitosan complex 2+The amount of substance is determined by the following formula: ; In the formula, Mn adsorbed by the iron-manganese modified chitosan complex 2+ Amount of substance, measured in mol; Mn in the MnCl2 aqueous solution before contact 2+ The molar concentration, expressed in mol / L; Mn in the liquid phase after contact 2+ The molar concentration is expressed in mol / L; V is the volume of the MnCl2 aqueous solution in L. Mn in all washing solutions 2+ The amount of substance, expressed in mol. The Mn in the washing solution... 2+ Subtracting this from the material balance results can reduce pore entrainment and unstable adsorption of Mn. 2+ The impact on the calculation of adsorption capacity.

[0060] Under the conditions described, It was 5.00 mmol / L. The concentration was 2.40 mmol / L, and the volume (V) was 0.500 L. The calculated value is 0.100 mmol. It was 1.20 mmol.

[0061] Adsorbed Mn 2+ The washed solids were dispersed in water and stirred at 25°C and 300 r / min. The adsorbed Mn was then dispersed... 2+ The amount of potassium permanganate added is determined by 2 / 3 of its molar amount. The feeding ratio of potassium permanganate is derived from the condition that MnO2 is the ideal product. 2+ The stoichiometric relationship with permanganate: ; This reaction formula is used to determine the initial amount of potassium permanganate to be added. It does not indicate that the second manganese oxide obtained from the reaction is entirely stoichiometric MnO2, nor is it used to determine the average manganese valence state and specific crystal form of the obtained second manganese oxide.

[0062] When the basic iron-manganese modified chitosan complex adsorbs Mn 2+When the amount of potassium permanganate was 1.20 mmol, 0.80 mmol was added. A 0.010 mol / L aqueous solution of potassium permanganate was prepared, corresponding to an addition volume of 80.0 mL. The potassium permanganate aqueous solution was added to the reaction system over 30 min, maintaining the pH of the system at 8.0 ± 0.2 using 0.1 mol / L sodium hydroxide solution during the addition. After the potassium permanganate aqueous solution was added, the reaction was continued for 2 h at 25 °C and 300 r / min.

[0063] Mn pre-adsorbed on the surface of the base complex 2+ It undergoes a redox reaction with permanganate ions, causing the second manganese oxide to preferentially react with Mn. 2+ Pre-adsorption sites are formed. H₂ is generated during the reaction. + Using sodium hydroxide to maintain the system pH can reduce localized acidification and the redissolution of the chitosan matrix under acidic conditions. Mn 2+ The relationship between the pre-adsorption location and the actual distribution of the second manganese oxide can be analyzed by combining the surface scan results of iron and manganese elements, but the specific spatial distance between the second manganese oxide and the iron oxide hydroxylide is not limited accordingly.

[0064] After the secondary manganese mineralization reaction, solid-liquid separation is performed. The obtained solid is washed with water to remove unreacted potassium permanganate, soluble manganese salts, and potassium salts, yielding the secondary manganese mineralization complex. During the washing process, the presence of free permanganate ions can be determined by the color of the washing solution and the detection of permanganate ions, and the manganese content in the washing solution can be determined by elemental analysis.

[0065] A portion of the secondary manganese mineralization complex was taken and its moisture content was determined. The amount of secondary manganese mineralization complex used in subsequent reactions was converted to dry weight. The secondary manganese mineralization complex was dispersed in water at a ratio of 50 mL of water to 1.00 g of dry weight secondary manganese mineralization complex.

[0066] The pH of the reaction system was adjusted to 8.3 ± 0.2 using a 0.1 mol / L sodium hydroxide solution. Glycidyltrimethylammonium chloride was added at a ratio of 0.030–0.122 g of active ingredient per 1.00 g dry-basis secondary manganese mineralization complex, maintaining the pH of the reaction system at 8.1–8.5 during the addition process. When using an aqueous solution of glycidyltrimethylammonium chloride, the amount of aqueous solution used was calculated based on the actual mass fraction of glycidyltrimethylammonium chloride in the solution.

[0067] The reaction system was placed at 60℃ and stirred at 300 r / min for 15 h. Maintaining the pH at 8.1–8.5 increased the proportion of chitosan amino groups in their unprotonated form. The unprotonated amino group nucleophilically attacked the epoxy carbon of glycidyltrimethylammonium chloride, opening the epoxy ring and forming a side group containing a 2-hydroxy-3-trimethylammoniumpropyl group on the chitosan matrix. The para ion of the quaternary ammonium cation was a chloride ion. The reaction proceeded according to the ring-opening reaction between the chitosan amino group and the epoxy group of glycidyltrimethylammonium chloride.

[0068] After the grafting reaction, solid-liquid separation was performed. The obtained solid was washed five times with water, each time using 20 mL of water per 1.00 g dry basis of the secondary manganese mineralization composite, to remove unreacted glycidyltrimethylammonium chloride, soluble chloride salts, and other water-soluble substances. The washed solid was vacuum dried at 60 °C for 12 h, pulverized, and passed through a 100-mesh sieve to obtain the iron-manganese modified chitosan composite material.

[0069] The side groups containing quaternary ammonium cations in the obtained composite material can be characterized by XPS N1s high-resolution spectroscopy. The XPS quaternary ammonium nitrogen ratio is expressed as the proportion of the fitted peak area of ​​quaternary ammonium nitrogen to the total fitted peak area of ​​N1s. The XPS quaternary ammonium nitrogen ratio reflects the relative composition of different nitrogen chemical states within the detection depth range of the material surface, and is not equivalent to the grafting rate of chitosan amino groups, nor is it directly calculated based on the amount of glycidyltrimethylammonium chloride added. XPS results should be analyzed in conjunction with thorough washing after the reaction, Cl2p signal, and other structural characterization results.

[0070] The resulting composite material contains ferrooxyhydroxylates with surface hydroxyl groups, which can provide surface binding sites for Sb(III) and Sb(V); manganese oxides can participate in the oxidation of Sb(III) and surface reactions of antimony species; and side groups containing quaternary ammonium cations introduce fixed positive charge sites into the material, which can react with Sb(OH)6. - Anionic antimony species undergo electrostatic interactions. The second manganese oxide, the side group containing quaternary ammonium cations, and the ferrooxy hydroxyl group are jointly loaded or grafted onto the chitosan matrix, providing structural conditions for the connection between Sb(III) oxidation, anionic antimony species interfacial enrichment, and antimony species fixation processes, but without limiting the specific spatial distance between the three types of sites or the microscopic migration path of antimony species.

[0071] The iron-manganese modified chitosan composite material can contact antimony-containing water, causing an interfacial reaction between the material and Sb(III) and Sb(V) in the water. After treatment, the material is separated from the water by filtration, centrifugation, or other solid-liquid separation methods. The composite material can also be mixed with antimony-contaminated soil, allowing the material to contact antimony species in the soil pore water. The Sb(III), Sb(V), and total antimony content in the water, as well as the extractable antimony and different forms of antimony content in the soil, should be determined using appropriate antimony speciation analysis and soil extraction analysis methods.

[0072] Example 1 This embodiment provides an iron-manganese modified chitosan composite material and its preparation method.

[0073] The iron-manganese modified chitosan composite material of this embodiment includes a chitosan matrix, an iron oxide hydroxyl group supported on the chitosan matrix, a first manganese oxide and a second manganese oxide, and a side group containing a quaternary ammonium cation grafted onto the chitosan matrix.

[0074] The ferric oxide hydroxylate is formed by the hydrolysis and condensation of ferric salt under alkaline conditions; the first manganese oxide is formed by the alkaline co-precipitation and aging process of divalent manganese salt; and the second manganese oxide is formed by Mn pre-adsorbed on the surface of the basic iron-manganese modified chitosan complex. 2+ It is formed by reacting with permanganate. Neither the first nor the second manganese oxide has a specific crystal form, average manganese valence state, or stoichiometric ratio.

[0075] The ferric oxide hydroxylate and the first manganese oxide are formed by co-precipitation of ferric salt, divalent manganese salt, and chitosan under alkaline conditions, with a Fe / Mn molar ratio of ferric salt to divalent manganese salt of 3:1. The side group containing the quaternary ammonium cation is formed by a ring-opening reaction between the epoxy group of glycidyltrimethylammonium chloride and some amino groups in the chitosan matrix. The side group containing the quaternary ammonium cation is 2-hydroxy-3-trimethylammoniumpropyl, and its counterpart is chloride ion.

[0076] In this embodiment, the amount of glycidyltrimethylammonium chloride active ingredient added is 0.0304 g per 1.00 g dry basis secondary manganese mineralization complex.

[0077] The iron-manganese modified chitosan composite material is prepared according to the following steps.

[0078] S1. Preparation of chitosan solution and iron-manganese salt solution Weigh 5.0 g of chitosan and place it in a 1000 mL beaker. Add 300 mL of 0.1 mol / L hydrochloric acid solution. Place the beaker in a 30°C constant temperature water bath and stir magnetically at 350 r / min until the chitosan is completely dissolved to obtain a chitosan solution.

[0079] Weigh 14.61 g of FeCl3·6H2O and 3.58 g of MnCl2·4H2O, add them to 300 mL of ultrapure water, and stir magnetically for 30 min at room temperature to completely dissolve the FeCl3·6H2O and MnCl2·4H2O, obtaining an iron-manganese salt solution. The molar ratio of Fe to Mn in the iron-manganese salt solution is 3:1.

[0080] S2. Preparation of basic iron-manganese modified chitosan complex The chitosan solution obtained in step S1 was placed in a 45°C constant temperature water bath and stirred at a speed of 350 r / min. The iron-manganese salt solution obtained in step S1 was added to the chitosan solution at a rate of 5 mL / min. After the iron-manganese salt solution was added, a 1 mol / L sodium hydroxide solution was slowly added to adjust the pH of the reaction system to 8.5–9.0.

[0081] The reaction was continued for 3 h at 45℃ and 350 r / min. During the reaction, a 1 mol / L sodium hydroxide solution was added to maintain the pH of the reaction system between 8.5 and 9.0.

[0082] After the reaction was completed, the reaction system was naturally cooled to room temperature and allowed to stand for 12 hours for aging. After aging, the solid was vacuum filtered and washed with ultrapure water until the pH of the washing solution was 7.0. The washed solid was then dried in a vacuum drying oven at 60°C for 12 hours, ground in an agate mortar and passed through a 100-mesh nylon sieve to obtain the basic iron-manganese modified chitosan complex.

[0083] S3. Pre-adsorption of Mn on the basic iron-manganese modified chitosan complex. 2+ Weigh 5.00 g of the basic iron-manganese modified chitosan complex obtained in step S2. Weigh 0.495 g of MnCl2·4H2O and dissolve it in 500 mL of ultrapure water to prepare the Mn... 2+ A 5.00 mmol / L aqueous solution of MnCl2.

[0084] The basic iron-manganese modified chitosan complex was added to the MnCl2 aqueous solution, and the pH of the reaction system was adjusted to 7.0 ± 0.2. The mixture was then contacted at 25 °C and 300 r / min for 2 h to allow the MnCl2 to react. 2+ It adsorbs onto the surface and accessible pores of the basic iron-manganese modified chitosan complex.

[0085] After contact, solid-liquid separation was performed, and the resulting liquid phase was collected. The solid was washed three times with 100 mL of ultrapure water each time, and all washing liquid was collected. Inductively coupled plasma atomic emission spectrometry was used to determine the Mn content in the MnCl2 aqueous solution before contact.2+ Concentration of Mn in the liquid phase after contact 2+ Concentration and Mn in all washing solutions 2+ content.

[0086] Mn adsorbed by the basic iron-manganese modified chitosan complex 2+ The amount of substance is calculated according to the following formula: n a =(C0-C e V-n_w; In the formula, n a Mn adsorbed by the iron-manganese modified chitosan complex 2+ Amount of substance, in mol; CO is the amount of Mn in the MnCl2 aqueous solution before contact. 2+ The molar concentration, in mol / L; C e Mn in the liquid phase after contact 2+ The molar concentration is expressed in mol / L; V is the volume of the MnCl2 aqueous solution in L; n_w is the total concentration of Mn in the washing solution. 2+ The amount of substance, expressed in mol.

[0087] The concentrations were determined to be C0 5.00 mmol / L, and C... e The concentration of Mn adsorbed by the basic iron-manganese modified chitosan complex was 2.40 mmol / L, V was 0.500 L, and n_w was 0.100 mmol. Based on the above formula, the concentration of Mn adsorbed by the basic iron-manganese modified chitosan complex was calculated. 2+ Amount of substance n a It was 1.20 mmol.

[0088] S4. Preparation of secondary manganese mineralization complex The adsorbed Mn obtained in step S3 2+ The washed solids were dispersed in 500 mL of ultrapure water and stirred at 25 °C and 300 r / min.

[0089] Prepare a 0.010 mol / L potassium permanganate aqueous solution. The amount of potassium permanganate is determined according to the following formula: n_KMnO4=2n a / 3; In the formula, n_KMnO4 is the amount of potassium permanganate, in mol; n a Mn adsorbed by the basic iron-manganese modified chitosan complex in step S3 2+ The amount of substance, measured in mol.

[0090] Based on n measured in step S3 aThe concentration was 1.20 mmol, and the calculated amount of potassium permanganate was 0.80 mmol. The volume of the 0.010 mol / L potassium permanganate aqueous solution added was 80.0 mL.

[0091] Take 80.0 mL of a 0.010 mol / L potassium permanganate aqueous solution and add it to adsorb Mn over 30 min. 2+ The reaction mixture was added to a dispersion of the iron-manganese modified chitosan complex. During the addition process, a 0.1 mol / L sodium hydroxide solution was used to maintain the pH of the reaction system at 8.0 ± 0.2. After the potassium permanganate aqueous solution was added, the reaction was continued at 25℃ and 300 r / min for 2 h.

[0092] After the reaction was completed, the mixture was vacuum filtered, and the resulting solid was washed with ultrapure water until no free permanganate ions were found in the washing solution, yielding a secondary manganese mineralization complex. A portion of the secondary manganese mineralization complex was taken to determine its water content, and the amount of secondary manganese mineralization complex used was converted to a dry basis mass.

[0093] S5. Partial cationization of the secondary manganese mineralization complex. Take the secondary manganese mineralization complex obtained in step S4, and weigh out an amount equivalent to 5.00 g of dry weight based on the measured moisture content.

[0094] Add 250 mL of ultrapure water at a ratio of 50 mL per 1.00 g dry-basis secondary manganese mineralization complex to disperse the secondary manganese mineralization complex in the ultrapure water. Adjust the pH of the reaction system to 8.3 ± 0.2 using a 0.1 mol / L sodium hydroxide solution.

[0095] Weigh 0.217 g of a 70.0% glycidyltrimethylammonium chloride aqueous solution, wherein the mass of the active ingredient of glycidyltrimethylammonium chloride is 0.152 g. Add the glycidyltrimethylammonium chloride aqueous solution to the reaction system, wherein the amount of active ingredient added is 0.0304 g per 1.00 g of dry basis secondary manganese mineralization complex. During the addition process, the pH value of the reaction system is maintained at 8.1–8.5 using a 0.1 mol / L sodium hydroxide solution.

[0096] After the aqueous solution of glycidyltrimethylammonium chloride was added, the reaction was carried out at 60℃ and 300 r / min for 15 h. The pH value of the reaction system was monitored during the reaction, and the pH value of the reaction system was maintained at 8.1–8.5 using a 0.1 mol / L sodium hydroxide solution.

[0097] After the reaction was completed, the solid was vacuum filtered and washed five times with 100 mL of ultrapure water each time. The washed solid was then dried in a vacuum drying oven at 60 °C for 12 h, ground in an agate mortar and passed through a 100-mesh nylon sieve to obtain the iron-manganese modified chitosan composite material.

[0098] Example 2 This embodiment provides an iron-manganese modified chitosan composite material and its preparation method.

[0099] The iron-manganese modified chitosan composite material of this embodiment includes a chitosan matrix, an iron oxide hydroxyl group supported on the chitosan matrix, a first manganese oxide and a second manganese oxide, and a side group containing a quaternary ammonium cation grafted onto the chitosan matrix.

[0100] The ferric oxide hydroxylate is formed by the hydrolysis and condensation of ferric salt under alkaline conditions; the first manganese oxide is formed by the alkaline co-precipitation and aging process of divalent manganese salt; and the second manganese oxide is formed by Mn pre-adsorbed on the surface of the basic iron-manganese modified chitosan complex. 2+ It is formed by reacting with permanganate. Neither the first nor the second manganese oxide has a specific crystal form, average manganese valence state, or stoichiometric ratio.

[0101] The ferric oxide hydroxylate and the first manganese oxide are formed by co-precipitation of ferric salt, divalent manganese salt, and chitosan under alkaline conditions, with a Fe / Mn molar ratio of ferric salt to divalent manganese salt of 3:1. The side group containing the quaternary ammonium cation is formed by a ring-opening reaction between the epoxy group of glycidyltrimethylammonium chloride and some amino groups in the chitosan matrix. The side group containing the quaternary ammonium cation is 2-hydroxy-3-trimethylammoniumpropyl, and its counterpart is chloride ion.

[0102] In this embodiment, the amount of glycidyltrimethylammonium chloride active ingredient added is 0.0606 g per 1.00 g dry basis secondary manganese mineralization complex.

[0103] The iron-manganese modified chitosan composite material is prepared according to the following steps.

[0104] S1. Preparation of chitosan solution and iron-manganese salt solution This step is exactly the same as in Example 1.

[0105] S2. Preparation of basic iron-manganese modified chitosan complex This step is exactly the same as in Example 1.

[0106] S3. Pre-adsorption of Mn on the basic iron-manganese modified chitosan complex. 2+ This step is exactly the same as in Example 1.

[0107] S4. Preparation of secondary manganese mineralization complex This step is exactly the same as in Example 1.

[0108] S5. Partial cationization of the secondary manganese mineralization complex. Take the secondary manganese mineralization complex obtained in step S4, and weigh out an amount equivalent to 5.00 g of dry weight based on the measured moisture content.

[0109] Add 250 mL of ultrapure water at a ratio of 50 mL per 1.00 g dry-basis secondary manganese mineralization complex to disperse the secondary manganese mineralization complex in the ultrapure water. Adjust the pH of the reaction system to 8.3 ± 0.2 using a 0.1 mol / L sodium hydroxide solution.

[0110] Weigh 0.433 g of a 70.0% (w / w) aqueous solution of glycidyltrimethylammonium chloride, wherein the mass of the active ingredient of glycidyltrimethylammonium chloride is 0.303 g. Add the aqueous solution of glycidyltrimethylammonium chloride to the reaction system, wherein the amount of active ingredient added is 0.0606 g per 1.00 g of dry basis secondary manganese mineralization complex. During the addition process, the pH value of the reaction system is maintained at 8.1–8.5 using a 0.1 mol / L sodium hydroxide solution.

[0111] After the aqueous solution of glycidyltrimethylammonium chloride was added, the reaction was carried out at 60℃ and 300 r / min for 15 h. The pH value of the reaction system was monitored during the reaction, and the pH value of the reaction system was maintained at 8.1–8.5 using a 0.1 mol / L sodium hydroxide solution.

[0112] After the reaction was completed, the solid was vacuum filtered and washed five times with 100 mL of ultrapure water each time. The washed solid was then dried in a vacuum drying oven at 60 °C for 12 h, ground in an agate mortar and passed through a 100-mesh nylon sieve to obtain the iron-manganese modified chitosan composite material.

[0113] Example 3 This embodiment provides an iron-manganese modified chitosan composite material and its preparation method.

[0114] The iron-manganese modified chitosan composite material of this embodiment includes a chitosan matrix, an iron oxide hydroxyl group supported on the chitosan matrix, a first manganese oxide and a second manganese oxide, and a side group containing a quaternary ammonium cation grafted onto the chitosan matrix.

[0115] The ferric oxide hydroxylate is formed by the hydrolysis and condensation of ferric salt under alkaline conditions; the first manganese oxide is formed by the alkaline co-precipitation and aging process of divalent manganese salt; and the second manganese oxide is formed by Mn pre-adsorbed on the surface of the basic iron-manganese modified chitosan complex. 2+ It is formed by reacting with permanganate. Neither the first nor the second manganese oxide has a specific crystal form, average manganese valence state, or stoichiometric ratio.

[0116] The ferric oxide hydroxylate and the first manganese oxide are formed by co-precipitation of ferric salt, divalent manganese salt, and chitosan under alkaline conditions, with a Fe / Mn molar ratio of ferric salt to divalent manganese salt of 3:1. The side group containing the quaternary ammonium cation is formed by a ring-opening reaction between the epoxy group of glycidyltrimethylammonium chloride and some amino groups in the chitosan matrix. The side group containing the quaternary ammonium cation is 2-hydroxy-3-trimethylammoniumpropyl, and its counterpart is chloride ion.

[0117] In this embodiment, the amount of glycidyltrimethylammonium chloride active ingredient added is 0.1214 g per 1.00 g dry basis secondary manganese mineralization complex.

[0118] The iron-manganese modified chitosan composite material is prepared according to the following steps.

[0119] S1. Preparation of chitosan solution and iron-manganese salt solution This step is exactly the same as in Example 1.

[0120] S2. Preparation of basic iron-manganese modified chitosan complex This step is exactly the same as in Example 1.

[0121] S3. Pre-adsorption of Mn on the basic iron-manganese modified chitosan complex. 2+ This step is exactly the same as in Example 1.

[0122] S4. Preparation of secondary manganese mineralization complex This step is exactly the same as in Example 1.

[0123] S5. Partial cationization of the secondary manganese mineralization complex. Take the secondary manganese mineralization complex obtained in step S4, and weigh out an amount equivalent to 5.00 g of dry weight based on the measured moisture content.

[0124] Add 250 mL of ultrapure water at a ratio of 50 mL per 1.00 g dry-basis secondary manganese mineralization complex to disperse the secondary manganese mineralization complex in the ultrapure water. Adjust the pH of the reaction system to 8.3 ± 0.2 using a 0.1 mol / L sodium hydroxide solution.

[0125] Weigh 0.867 g of a 70.0% glycidyltrimethylammonium chloride aqueous solution, wherein the mass of the active ingredient of glycidyltrimethylammonium chloride is 0.607 g. Add the glycidyltrimethylammonium chloride aqueous solution to the reaction system, wherein the amount of active ingredient added is 0.1214 g per 1.00 g of dry basis secondary manganese mineralization complex. During the addition process, the pH value of the reaction system is maintained at 8.1–8.5 using a 0.1 mol / L sodium hydroxide solution.

[0126] After the aqueous solution of glycidyltrimethylammonium chloride was added, the reaction was carried out at 60℃ and 300 r / min for 15 h. The pH value of the reaction system was monitored during the reaction, and the pH value of the reaction system was maintained at 8.1–8.5 using a 0.1 mol / L sodium hydroxide solution.

[0127] After the reaction was completed, the solid was vacuum filtered and washed five times with 100 mL of ultrapure water each time. The washed solid was then dried in a vacuum drying oven at 60 °C for 12 h, ground in an agate mortar and passed through a 100-mesh nylon sieve to obtain the iron-manganese modified chitosan composite material.

[0128] Comparative Example 1 This comparative example provides an iron-manganese modified chitosan material and its preparation method.

[0129] The iron-manganese modified chitosan material of this comparative example includes a chitosan matrix and an iron oxide hydroxylide and a first manganese oxide supported on the chitosan matrix. The iron oxide hydroxylide is formed by the hydrolysis and condensation of a trivalent iron salt under alkaline conditions, and the first manganese oxide is formed by the alkaline co-precipitation and aging process of a divalent manganese salt. The specific crystal forms and stoichiometric ratios of the iron oxide hydroxylide and the first manganese oxide are not limited.

[0130] The ferric oxide hydroxylate and the first manganese oxide are formed by co-precipitation of ferric salt, divalent manganese salt, and chitosan under alkaline conditions, with a Fe / Mn molar ratio of ferric salt to divalent manganese salt of 3:1. This comparative example does not involve Mn precipitation. 2+ Pre-adsorption and secondary manganese mineralization are not used, nor is partial cationization of the chitosan matrix performed using glycidyltrimethylammonium chloride.

[0131] The iron-manganese modified chitosan material is prepared according to the following steps.

[0132] S1. Preparation of chitosan solution and iron-manganese salt solution This step is exactly the same as in Example 1.

[0133] S2. Preparation of basic iron-manganese modified chitosan complex This step is exactly the same as in Example 1.

[0134] The basic iron-manganese modified chitosan composite obtained in step S2 was used as the iron-manganese modified chitosan material in this comparative example.

[0135] Comparative Example 2 This comparative example provides an iron-manganese modified chitosan material directly treated with potassium permanganate and its preparation method.

[0136] The iron-manganese modified chitosan material in this comparative example uses a basic iron-manganese modified chitosan complex as the treatment object. This basic iron-manganese modified chitosan complex includes a chitosan matrix and ferric oxide hydroxylates and a first manganese oxide supported on the chitosan matrix. The ferric oxide hydroxylates are formed by the hydrolysis and condensation of trivalent iron salts under alkaline conditions, and the first manganese oxide is formed by the alkaline co-precipitation and aging process of divalent manganese salts.

[0137] The ferric oxide hydroxylate and the first manganese oxide are formed by co-precipitation of ferric salt, divalent manganese salt, and chitosan under alkaline conditions, with a Fe / Mn molar ratio of ferric salt to divalent manganese salt of 3:1. This comparative example does not involve Mn precipitation. 2+ Pre-adsorption was performed by directly treating the basic iron-manganese modified chitosan complex with potassium permanganate. The manganese-containing surface reaction products formed during this treatment process did not conform to the Mn... 2+ The amount of pre-adsorption was controlled. This comparative example did not use glycidyltrimethylammonium chloride to partially cationize the chitosan matrix.

[0138] The iron-manganese modified chitosan material directly treated with potassium permanganate was prepared according to the following steps.

[0139] S1. Preparation of chitosan solution and iron-manganese salt solution This step is exactly the same as in Example 1.

[0140] S2. Preparation of basic iron-manganese modified chitosan complex This step is exactly the same as in Example 1.

[0141] S3. Direct treatment of the basic iron-manganese modified chitosan complex with potassium permanganate. Weigh 5.00 g of the basic iron-manganese modified chitosan complex obtained in step S2, disperse it in 500 mL of ultrapure water, and stir at 25 °C and 300 r / min.

[0142] Take 80.0 mL of a 0.010 mol / L potassium permanganate aqueous solution, wherein the amount of potassium permanganate is 0.80 mmol, which is the same amount of potassium permanganate used in step S4 of Example 1 when treating 5.00 g of basic iron-manganese modified chitosan complex.

[0143] The potassium permanganate aqueous solution was added to the basic iron-manganese modified chitosan complex dispersion over 30 min. During the addition, the pH of the reaction system was maintained at 8.0 ± 0.2 using a 0.1 mol / L sodium hydroxide solution. After the potassium permanganate aqueous solution was added, the reaction was continued for 2 h at 25 °C and 300 r / min.

[0144] After the reaction was completed, the solid was vacuum filtered and washed with ultrapure water until no free permanganate ions were found in the washing solution. The washed solid was then dried in a vacuum drying oven at 60°C for 12 h, ground in an agate mortar and passed through a 100-mesh nylon sieve to obtain iron-manganese modified chitosan material directly treated with potassium permanganate.

[0145] Comparative Example 3 This comparative example provides a secondary manganese mineralization iron-manganese modified chitosan composite material and its preparation method.

[0146] This comparative example of a secondary manganese mineralization iron-manganese modified chitosan composite material includes a chitosan matrix and ferric oxide hydroxylates, a first manganese oxide, and a second manganese oxide supported on the chitosan matrix. The ferric oxide hydroxylates are formed by the hydrolysis and condensation of trivalent ferric salts under alkaline conditions. The first manganese oxide is formed by the alkaline co-precipitation and aging process of divalent manganese salts. The second manganese oxide is formed by Mn2 pre-adsorbed onto the surface of the basic iron-manganese modified chitosan composite. 2+ It is formed by reacting with permanganate. Neither the first nor the second manganese oxide has a specific crystal form, average manganese valence state, or stoichiometric ratio.

[0147] The ferric oxide hydroxylate and the first manganese oxide are formed by co-precipitation of trivalent ferric salt, divalent manganese salt, and chitosan under alkaline conditions, with a Fe / Mn molar ratio of ferric salt to divalent manganese salt of 3:1. This comparative example involves Mn... 2+ Pre-adsorption and secondary manganese mineralization are performed without the use of glycidyltrimethylammonium chloride for partial cationization of the chitosan matrix.

[0148] The secondary manganese mineralization iron-manganese modified chitosan composite material is prepared according to the following steps.

[0149] S1. Preparation of chitosan solution and iron-manganese salt solution This step is exactly the same as in Example 1.

[0150] S2. Preparation of basic iron-manganese modified chitosan complex This step is exactly the same as in Example 1.

[0151] S3. Pre-adsorption of Mn on the basic iron-manganese modified chitosan complex. 2+ This step is exactly the same as in Example 1.

[0152] S4. Preparation of secondary manganese mineralization iron-manganese modified chitosan composite material The adsorbed Mn obtained in step S3 2+ The washed solids were dispersed in 500 mL of ultrapure water and stirred at 25 °C and 300 r / min.

[0153] Based on the measurement results of step S3 in Example 1, the Mn adsorbed by the basic iron-manganese modified chitosan complex... 2+ Amount of substance n a The concentration was 1.20 mmol. Based on the molar amount of potassium permanganate, the adsorption of Mn... 2+ Based on a molar ratio of 2 / 3, the amount of potassium permanganate added is 0.80 mmol.

[0154] Take 80.0 mL of a 0.010 mol / L potassium permanganate aqueous solution and add it to adsorb Mn over 30 min. 2+ The reaction mixture was added to a dispersion of the iron-manganese modified chitosan complex. During the addition process, a 0.1 mol / L sodium hydroxide solution was used to maintain the pH of the reaction system at 8.0 ± 0.2. After the potassium permanganate aqueous solution was added, the reaction was continued at 25℃ and 300 r / min for 2 h.

[0155] After the reaction was completed, the solid was vacuum filtered and washed with ultrapure water until no free permanganate ions were found in the washing solution. The washed solid was then dried in a vacuum drying oven at 60°C for 12 h, ground with an agate mortar and passed through a 100-mesh nylon sieve to obtain a secondary manganese mineralized iron-manganese modified chitosan composite material.

[0156] Comparative Example 4 This comparative example provides a partially cationic iron-manganese modified chitosan composite material and its preparation method.

[0157] The partially cationic iron-manganese modified chitosan composite material of this comparative example includes a chitosan matrix, an iron oxide hydroxyl group and a first manganese oxide loaded on the chitosan matrix, and a side group containing quaternary ammonium cations grafted onto the chitosan matrix.

[0158] The ferric oxide hydroxylate is formed by the hydrolysis and condensation of ferric salt under alkaline conditions, and the first manganese oxide is formed by the alkaline co-precipitation and aging process of divalent manganese salt. The side group containing the quaternary ammonium cation is formed by the ring-opening reaction of the epoxy group of glycidyltrimethylammonium chloride with some amino groups in the chitosan matrix, and the side group containing the quaternary ammonium cation is 2-hydroxy-3-trimethylammoniumpropyl, whose parallel ion is chloride ion.

[0159] The ferric oxide hydroxylate and the first manganese oxide are formed by co-precipitation of ferric salt, divalent manganese salt, and chitosan under alkaline conditions, with a Fe / Mn molar ratio of ferric salt to divalent manganese salt of 3:1. This comparative example does not involve Mn precipitation. 2+ Pre-adsorption and secondary manganese mineralization directly partially cationize the basic iron-manganese modified chitosan complex. The amount of glycidyltrimethylammonium chloride active ingredient added is 0.0304 g per 1.00 g dry basis basic iron-manganese modified chitosan complex, which is the same as the dry basis feeding ratio used in Example 1.

[0160] The partially cationic iron-manganese modified chitosan composite material is prepared according to the following steps.

[0161] S1. Preparation of chitosan solution and iron-manganese salt solution This step is exactly the same as in Example 1.

[0162] S2. Preparation of basic iron-manganese modified chitosan complex This step is exactly the same as in Example 1.

[0163] S3. Partial cationization of the basic iron-manganese modified chitosan complex. Weigh 5.00 g of the basic iron-manganese modified chitosan complex obtained in step S2, add 250 mL of ultrapure water, and disperse at 300 r / min. Adjust the pH of the reaction system to 8.3 ± 0.2 using a 0.1 mol / L sodium hydroxide solution.

[0164] Weigh 0.217 g of a 70.0% glycidyltrimethylammonium chloride aqueous solution, wherein the mass of the active ingredient of glycidyltrimethylammonium chloride is 0.152 g. Add the glycidyltrimethylammonium chloride aqueous solution to the reaction system, wherein the amount of active ingredient added is 0.0304 g per 1.00 g of dry basis iron-manganese modified chitosan complex. During the addition process, the pH value of the reaction system is maintained at 8.1–8.5 using a 0.1 mol / L sodium hydroxide solution.

[0165] After the aqueous solution of glycidyltrimethylammonium chloride was added, the reaction was carried out at 60℃ and 300 r / min for 15 h. The pH value of the reaction system was monitored during the reaction, and the pH value of the reaction system was maintained at 8.1–8.5 using a 0.1 mol / L sodium hydroxide solution.

[0166] After the reaction was completed, the solid was vacuum filtered and washed five times with 100 mL of ultrapure water each time. The washed solid was then dried in a vacuum drying oven at 60 °C for 12 h, ground in an agate mortar and passed through a 100-mesh nylon sieve to obtain a partially cationic iron-manganese modified chitosan composite material.

[0167] Comparative Example 5 This comparative example provides an iron-manganese modified chitosan composite material with altered secondary manganese mineralization and partial cationization sequence, and its preparation method.

[0168] The iron-manganese modified chitosan composite material of this comparative example includes a chitosan matrix, an iron oxide hydroxyl group supported on the chitosan matrix, a first manganese oxide and a second manganese oxide, and a side group containing a quaternary ammonium cation grafted onto the chitosan matrix.

[0169] The ferric oxide hydroxylate is formed by the hydrolysis and condensation of ferric salt under alkaline conditions, and the first manganese oxide is formed by the alkaline co-precipitation and aging process of divalent manganese salt. The side group containing the quaternary ammonium cation is formed by the ring-opening reaction of the epoxy group of glycidyltrimethylammonium chloride with some amino groups in the chitosan matrix. The side group containing the quaternary ammonium cation is 2-hydroxy-3-trimethylammoniumpropyl, and its counterpart ion is chloride ion. The second manganese oxide is formed by Mn pre-adsorbed on the surface of the partially cationic iron-manganese modified chitosan complex. 2+ It is formed by reacting with permanganate.

[0170] The ferric oxide hydroxylate and the first manganese oxide are formed by co-precipitation of trivalent ferric salt, divalent manganese salt, and chitosan under alkaline conditions, with a Fe / Mn molar ratio of 3:1 for the trivalent ferric salt and divalent manganese salt. In this comparative example, the basic iron-manganese modified chitosan complex was first partially cationized using glycidyltrimethylammonium chloride, followed by Mn... 2+ Pre-adsorption and secondary manganese mineralization. The amount of glycidyltrimethylammonium chloride active ingredient added is 0.0304 g per 1.00 g dry basis iron-manganese modified chitosan complex.

[0171] The iron-manganese modified chitosan composite material is prepared according to the following steps.

[0172] S1. Preparation of chitosan solution and iron-manganese salt solution This step is exactly the same as in Example 1.

[0173] S2. Preparation of basic iron-manganese modified chitosan complex This step is exactly the same as in Example 1.

[0174] S3. Partial cationization of the basic iron-manganese modified chitosan complex. Weigh 5.00 g of the basic iron-manganese modified chitosan complex obtained in step S2, add 250 mL of ultrapure water, and disperse at 300 r / min. Adjust the pH of the reaction system to 8.3 ± 0.2 using a 0.1 mol / L sodium hydroxide solution.

[0175] Weigh 0.217 g of a 70.0% glycidyltrimethylammonium chloride aqueous solution, wherein the mass of the active ingredient of glycidyltrimethylammonium chloride is 0.152 g. Add the glycidyltrimethylammonium chloride aqueous solution to the reaction system, wherein the amount of active ingredient added is 0.0304 g per 1.00 g of dry basis iron-manganese modified chitosan complex. During the addition process, the pH value of the reaction system is maintained at 8.1–8.5 using a 0.1 mol / L sodium hydroxide solution.

[0176] After the aqueous solution of glycidyltrimethylammonium chloride was added, the reaction was carried out at 60℃ and 300 r / min for 15 h. The pH value of the reaction system was monitored during the reaction, and the pH value of the reaction system was maintained at 8.1–8.5 using a 0.1 mol / L sodium hydroxide solution.

[0177] After the reaction was completed, the solid was vacuum filtered and washed five times with 100 mL of ultrapure water each time. The washed solid was then dried in a vacuum drying oven at 60 °C for 12 h, ground in an agate mortar and passed through a 100-mesh nylon sieve to obtain a partially cationic iron-manganese modified chitosan complex.

[0178] S4. Pre-adsorption of Mn on partially cationic iron-manganese modified chitosan complex 2+

[0179] Weigh 5.00 g of the partially cationic iron-manganese modified chitosan complex obtained in step S3. Weigh 0.495 g of MnCl2·4H2O and dissolve it in 500 mL of ultrapure water to prepare the Mn... 2+ A 5.00 mmol / L aqueous solution of MnCl2.

[0180] A portion of the cationic iron-manganese modified chitosan complex was added to the MnCl2 aqueous solution, and the pH of the reaction system was adjusted to 7.0 ± 0.2. The mixture was then contacted at 25 °C and 300 r / min for 2 h to allow the MnCl2 to react. 2+ It is adsorbed on the surface and in the accessible pores of the partially cationic iron-manganese modified chitosan complex.

[0181] After contact, solid-liquid separation was performed, and the resulting liquid phase was collected. The solid was washed three times with 100 mL of ultrapure water each time, and all washing liquid was collected. Inductively coupled plasma atomic emission spectrometry was used to determine the Mn content in the MnCl2 aqueous solution before contact. 2+ Concentration of Mn in the liquid phase after contact 2+ Concentration and Mn in all washing solutions 2+ content.

[0182] Mn adsorbed by partially cationic iron-manganese modified chitosan complex 2+ The amount of substance is calculated according to the following formula: n a ′=(C0-C e ′)V-n_w′; In the formula, n a ′ represents Mn adsorbed by a partially cationic iron-manganese modified chitosan complex. 2+ Amount of substance, in mol; CO is the amount of Mn in the MnCl2 aqueous solution before contact. 2+ The molar concentration, in mol / L; C e ′ represents Mn in the liquid phase after contact 2+ The molar concentration is expressed in mol / L; V is the volume of the MnCl2 aqueous solution, which is 0.500 L in this comparative example; n_w′ is the total concentration of MnCl2 in the washing solution. 2+ The amount of substance, expressed in mol.

[0183] S5, for adsorbing Mn 2+ The subsequent partial cationized iron-manganese modified chitosan complex underwent secondary manganese mineralization. The adsorbed Mn obtained in step S4 2+ The washed solids were dispersed in 500 mL of ultrapure water and stirred at 25 °C and 300 r / min.

[0184] Prepare a 0.010 mol / L potassium permanganate aqueous solution. The amount of potassium permanganate is determined according to the following formula: n_KMnO4=2n a ′ / 3; In the formula, n_KMnO4 is the amount of potassium permanganate, in mol; n a ′ represents the Mn adsorbed by the partially cationic iron-manganese modified chitosan complex in step S4. 2+ The amount of substance, measured in mol.

[0185] The volume of potassium permanganate aqueous solution added is determined according to the following formula: V_KMnO4=n_KMnO4 / 0.010; In the formula, V_KMnO4 is the volume of potassium permanganate aqueous solution added, in L.

[0186] The calculated amount of potassium permanganate aqueous solution was added to adsorb Mn within 30 min. 2+ The cationized iron-manganese modified chitosan complex was added to the dispersion. During the addition process, the pH of the reaction system was maintained at 8.0 ± 0.2 using a 0.1 mol / L sodium hydroxide solution. After the potassium permanganate aqueous solution was added, the reaction continued for 2 hours at 25℃ and 300 r / min.

[0187] After the reaction was completed, the solid was vacuum filtered and washed with ultrapure water until no free permanganate ions were found in the washing solution. The washed solid was then dried in a vacuum drying oven at 60°C for 12 h, ground with an agate mortar and passed through a 100-mesh nylon sieve to obtain an iron-manganese modified chitosan composite material with altered secondary manganese mineralization and partial cationization sequence.

[0188] To verify the technical effect of the present invention, the test samples were prepared as follows: Chitosan, FeCl3·6H2O, MnCl2·4H2O, potassium permanganate, and glycidyltrimethylammonium chloride from the same batch were selected, and corresponding iron-manganese modified chitosan materials were prepared according to the complete processes described in Examples 1, 2, 3, and Comparative Examples 1, 2, 3, 4, and 5. After each group of materials underwent the corresponding treatment, they were vacuum dried at 60°C for 12 h, ground, and passed through a 100-mesh nylon sieve. They were then sealed and stored under dry conditions and sequentially labeled as FMCS1001 to FMCS1008. Subsequent tests were conducted using samples taken from the same dry basis mass of the materials. Three parallel experiments were set up for each test, and the test results were expressed as the arithmetic mean of the parallel experiments.

[0189] Material structure and composition characterization Materials prepared in Example 1, Comparative Example 1, Comparative Example 3, and Comparative Example 4 were subjected to scanning electron microscopy and energy dispersive spectroscopy (EDS) analysis. After vacuum drying at 60°C, the samples were fixed on a conductive sample stage and subjected to gold or carbon sputtering treatment according to their conductivity. Following the data acquisition and quantitative analysis requirements specified in GB / T 17359—2023 "Quantitative Analysis of Elements with Atomic Numbers Not Less Than 11 by Energy Dispersive Spectroscopy Using Microbeam Analysis", the surface morphology of the materials was observed using scanning electron microscopy, and elemental surface scans of Fe and Mn at the same magnification were acquired. The Fe and Mn elemental surface scans were used to compare the basic co-precipitation and Mn... 2+ The distribution of iron and manganese components after pre-adsorption, secondary manganese mineralization, partial cationization, and the complete treatment route is determined without relying on energy dispersive spectroscopy (EDS) results to determine the specific valence state of manganese.

[0190] X-ray diffraction tests were performed on the materials prepared in Example 1, Comparative Example 1, and Comparative Example 3, respectively. Following GB / T30904—2014 "X-ray Diffraction Method for Crystal Structure Analysis of Inorganic Chemical Products", the dried samples were finely ground and placed in a sample cell. Cu Kα rays were used to collect X-ray diffraction patterns within the range of 5° to 80° 2θ. The obtained patterns were used to compare the diffraction peaks and phase changes before and after secondary manganese mineralization. Because manganese oxides may have low crystallinity, mixed valence states, or non-stoichiometric compositions, the X-ray diffraction results were only used to analyze identifiable crystal phase characteristics and were not used alone to determine the average manganese valence state and stoichiometric ratio of the first and second manganese oxides.

[0191] Materials prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were subjected to X-ray photoelectron spectroscopy (XPS) analysis. Test and data processing conditions were recorded according to GB / T 33502—2017 "Specification Requirements for Data Recording and Reporting of X-ray Photoelectron Spectroscopy (XPS) for Surface Chemical Analysis," and N1s high-resolution spectra were processed according to GB / T 41073—2021 "Basic Requirements for Peak Fitting Reports of X-ray Photoelectron Spectroscopy for Surface Chemical Analysis." Monochromatic Al Kα rays were used to acquire the full XPS spectrum and N1s high-resolution spectra. The binding energy was corrected using the C-C / C-H components in the C1s spectrum, and the same background subtraction method and peak shape function were used to fit each group of N1s spectra. The XPS quaternary ammonium nitrogen ratio was expressed as the proportion of the fitted peak area of ​​quaternary ammonium nitrogen to the total fitted peak area of ​​N1s. This ratio reflects the relative proportion of quaternary ammonium nitrogen components to all nitrogen components within the XPS detection depth range and is not equivalent to the grafting rate of chitosan amino groups. The XPS full spectrum, N1s high-resolution spectrum, and Cl2p spectrum of Example 1 and Comparative Example 1 were selected as representative spectra. The XPS quaternary ammonium nitrogen ratios of the other samples are listed in Table 1.

[0192] Materials prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were subjected to nitrogen adsorption tests according to GB / T19587—2017 "Determination of Specific Surface Area of ​​Solid Substances by Gas Adsorption BET Method". The samples were degassed under vacuum without altering the chitosan structure. Nitrogen adsorption-desorption data were collected at liquid nitrogen temperature, and the specific surface area was calculated using the BET method. The specific surface area retention rate was calculated as the ratio of the BET specific surface area of ​​each treatment group to the BET specific surface area of ​​Comparative Example 1. A higher specific surface area retention rate indicates a higher degree of retention of the accessible surface area after secondary manganese mineralization and partial cationization.

[0193] The above tests characterize the material's surface morphology, iron and manganese element distribution, identifiable phases, surface nitrogen chemical state, and specific surface area. All results should be analyzed in conjunction with each other; do not determine the manganese valence state, GTMAC grafting rate, or specific spatial distances between different reaction sites based solely on a single test.

[0194] Sb(III) and Sb(V) adsorption performance test Test solutions with Sb(III) and Sb(V) as the initial antimony forms were prepared separately, and each group of tests was conducted separately. The total dissolved antimony concentration in the liquid phase was determined according to HJ 694—2014 "Determination of Mercury, Arsenic, Selenium, Bismuth and Antimony in Water by Atomic Fluorescence Method". When the sample concentration exceeded the calibration range of this method, quantitative dilution with experimental water was performed to bring the antimony concentration in the test solution into the calibration range, and the dilution factor was included in the final result. The total dissolved antimony concentration obtained by this method is not used alone to determine the valence state conversion ratio between Sb(III) and Sb(V) during the test.

[0195] Weigh 0.0500 g of the materials prepared in Examples 1 to 3 and Comparative Examples 1 to 5, respectively, and add them to 50.0 mL of Sb(III) or Sb(V) solution with an initial concentration of 100 mg / L. Adjust the pH of the test solution to 7.0 ± 0.1 using hydrochloric acid solution or sodium hydroxide solution, and shake for 24 h at 25 ± 1 °C and 200 r / min. After adsorption is complete, centrifuge or filter, and determine the antimony concentration of the separated liquid phase.

[0196] The equilibrium adsorption capacity is calculated using the following formula: q e =(C0-C e V / m; The removal rate is calculated using the following formula: η=(C0-C e ) / C0×100%; In the formula, q e To determine the equilibrium adsorption capacity, the unit is mg / g; CO and C e V represents the antimony concentration in the liquid phase before and after adsorption, in mg / L; V is the volume of the antimony solution, in L; m is the dry mass of the material, in g; and η is the removal rate.

[0197] The equilibrium adsorption capacity represents the amount of antimony removed from the liquid phase by a unit mass of material under specified conditions, while the removal rate represents the percentage decrease in the concentration of antimony in the liquid phase under a specified material dosage.

[0198] Initial Sb(III) or Sb(V) concentration gradients of 5 mg / L, 10 mg / L, 25 mg / L, 50 mg / L, 75 mg / L, 100 mg / L, 150 mg / L, and 200 mg / L were set for Examples 1 to 3 and Comparative Examples 1 to 5, respectively. Material mass, solution volume, pH value, temperature, oscillation speed, and adsorption time were kept consistent. Based on the equilibrium concentration and equilibrium adsorption capacity at each initial concentration, Langmuir and Freundlich isotherm models were fitted using nonlinear methods to obtain the fitted adsorption capacity and related parameters. The isotherm adsorption fitting curves of Example 1 and Comparative Example 1 were selected as representative curves, and the fitted adsorption capacities of the remaining samples are listed in Table 1. The fitted adsorption capacity is used to compare the antimony loading capacity of each group of materials within the specified concentration range and under the test conditions, and is not considered as the actual adsorption capacity outside the stated test conditions.

[0199] Adsorption kinetics performance test The total dissolved antimony concentration in the liquid phase was determined according to HJ 694—2014 "Determination of Mercury, Arsenic, Selenium, Bismuth and Antimony in Water by Atomic Fluorescence Method". 0.0500 g of the materials prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were weighed and added to 50.0 mL of Sb(III) or Sb(V) solution with an initial concentration of 1.00 mg / L. The pH of the solution was adjusted to 7.0±0.1, and the solution was shaken at 25±1℃ and 200 r / min. Samples were taken at 5 min, 15 min, 30 min, 60 min, 120 min, 180 min, 240 min, 300 min, 360 min, 420 min, 480 min, 540 min, 600 min, 720 min, and 1440 min.

[0200] Solid-liquid separation was performed immediately after each sampling, and the antimony concentration in the liquid phase was measured. The adsorption amount at each time point was calculated using the following formula: q t =(C0-C t) V / m; In the formula, q t Ct represents the amount of antimony adsorbed at time t, in mg / g; C0 represents the concentration of antimony in the liquid phase before adsorption, in mg / L; Ct represents the amount of antimony adsorbed at time t, in mg / g; Ct represents the concentration of antimony in the liquid phase before adsorption, in mg / L; Ct represents the amount of antimony t t represents the concentration of antimony in the liquid phase at time t, in mg / L; V represents the volume of the antimony solution, in L; and m represents the dry mass of the material, in g.

[0201] Parallel reaction vessels were used at each sampling time point to avoid changes in solution volume and solid-liquid ratio caused by continuous sampling. The adsorption amount at 1440 min was taken as the final stable adsorption amount under the experimental conditions. When the adsorption amount at a certain sampling time and at each subsequent sampling time deviated from the adsorption amount at 1440 min by no more than 5%, that sampling time was determined as the adsorption equilibrium time, and the proportion of the adsorption amount at 120 min to that at 1440 min was calculated. The shorter the adsorption equilibrium time and the greater the adsorption amount within the same time period, the faster the material removes antimony from the liquid phase under the specified conditions.

[0202] Adsorption kinetic data were fitted using pseudo-first-order and pseudo-second-order kinetic models. The fitting results of the kinetic models are used to describe the change in adsorption amount over time and are not used as the sole basis for determining the mechanism of chemisorption, physisorption, or Sb(III) oxidation. The kinetic fitting curves of Example 1 and Comparative Example 1 were selected as representative curves, and the adsorption equilibrium times of the remaining samples are listed in Table 1.

[0203] Cyclic adsorption performance test 0.0500 g of the materials prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were weighed and added to 50.0 mL of Sb(III) or Sb(V) solution with an initial concentration of 10.0 mg / L, respectively. Adsorption was carried out for 24 h under the conditions of pH 7.0±0.1, temperature 25±1℃, and shaking speed 200 r / min. After adsorption, solid-liquid separation was performed. The antimony concentration in the liquid phase was determined according to HJ 694—2014 "Determination of Mercury, Arsenic, Selenium, Bismuth and Antimony in Water by Atomic Fluorescence Method", and the equilibrium adsorption capacity of this cycle was calculated.

[0204] The solid obtained after adsorption and separation was added to 50.0 mL of 0.1 mol / L NaOH solution and desorbed for 12 h at 25±1℃ and 200 r / min. After desorption, solid-liquid separation was performed, and the antimony concentration in the eluent was measured. The desorbed material was washed with water until the pH of the washing solution was 7.0±0.2, and then vacuum dried at 60℃ for 12 h. The dry basis mass of the recovered material was recorded before proceeding to the next adsorption experiment. The adsorption capacity of each cycle was calculated based on the actual dry basis mass of the material at the start of that cycle, and five adsorption-desorption cycles were performed consecutively.

[0205] The adsorption capacity retention rate after the fifth cycle is calculated according to the following formula: R = q5 / q1 × 100%; In the formula, R is the adsorption capacity retention rate after the fifth cycle; q1 and q5 are the equilibrium adsorption amounts in the first and fifth cycles, respectively, in mg / g.

[0206] The adsorption capacity retention rate indicates the degree to which the material retains its adsorption capacity per unit mass after repeated adsorption, alkaline desorption, water washing, and drying. This indicator is affected by changes in active sites, leaching of inorganic components, material loss, and repeated drying, and cannot be used alone as proof that the material structure has not changed. Representative curves were plotted based on the adsorption results of five cycles for Example 1 and Comparative Example 1. The adsorption capacity retention rates of the remaining samples after the fifth cycle are listed in Table 1.

[0207] Soil antimony passivation performance test Currently, there are no GB / T or HJ standards that directly specify the extraction method for extractable antimony from soil using 0.01 mol / L CaCl2. This experiment uses a standardized laboratory extraction method to evaluate the changes in extractable antimony from soil before and after different material treatments, maintaining consistent extractant concentration, soil-liquid ratio, temperature, shaking time, and separation conditions.

[0208] Artificially contaminated antimony soil from the same batch was selected. The artificially contaminated antimony soil was aged for 30 days before material treatment, and the extractable antimony content in CaCl2 of the soil after aging was 20.0 mg / kg. A blank group without added materials and treatment groups with materials prepared according to Examples 1 to 3 and Comparative Examples 1 to 5 were set up. The amount of material added to each group was calculated based on the dry weight of the soil, and three parallel experiments were set up for each group.

[0209] Example 1 and Comparative Example 1 were set with material dosages of 0.1%, 0.3%, and 0.5%, respectively, to compare the effects of material dosage and incubation time; Example 2, Example 3, and Comparative Examples 2 to 5 used a material dosage of 0.3% to compare the soil antimony passivation performance of different materials at the same dosage.

[0210] The materials were thoroughly mixed with the soil, and the soil moisture content was adjusted to 60% of field capacity. The mixture was then incubated at 25±2℃ for 35 days. Samples were taken from the control group, each dosage group in Example 1, and each dosage group in Comparative Example 1 at 0, 7, 14, 21, 28, and 35 days of incubation, respectively. Samples were taken from the remaining material treatment groups after 35 days of incubation.

[0211] Take 5.00 g of air-dried soil sample that has passed through a 2 mm sieve, add 50.0 mL of 0.01 mol / L CaCl2 solution, and shake for 2 h at 20±2℃ and 180 r / min. After shaking, centrifuge and filter the supernatant. The antimony concentration in the CaCl2 extract was determined by atomic fluorescence spectrometry according to HJ 694—2014. Before the determination, CaCl2 solution blank, soil matrix blank, and spiked recovery tests were set up; when the antimony concentration in the extract exceeded the calibration range, quantitative dilution was performed. Based on the antimony concentration in the extract, the extract volume, and the dry basis mass of the soil, the extractable antimony content per unit mass of soil was calculated.

[0212] Total antimony in the soil was determined according to HJ 680—2013 "Determination of Mercury, Arsenic, Selenium, Bismuth and Antimony in Soils and Sediments by Microwave Digestion / Atomic Fluorescence Method", and soil pH was determined according to HJ 962—2018 "Determination of Soil pH by Potentiometric Method".

[0213] Soil antimony passivation rate is calculated using the following formula: ; In the formula, P is the antimony passivation rate of the soil; The extractable antimony content in soil CaCl2 at the start of cultivation was 20.00 mg / kg in this experiment; The extractable antimony content in CaCl2 of the corresponding treatment group after cultivation for a specified time.

[0214] A lower content of extractable antimony in CaCl2 and a higher passivation rate indicate that less antimony can be extracted from the soil by dilute salt solution under specified cultivation conditions. This indicator is used to compare the degree to which different materials immobilize easily migratable antimony components in the soil, and is not directly equivalent to the content of antimony that plants can absorb. The range of soil pH change is used to evaluate the impact of material treatments on the soil's acid-base environment.

[0215] The changes in extractable antimony content and passivation rate of CaCl2 during 35 days of cultivation were plotted for the blank group, the 0.3% dosage group of Comparative Example 1, and the 0.3% dosage group of Example 1 to Example 3 and Comparative Examples 1 to 5 after 35 days of cultivation at a 0.3% dosage. Table 2 shows the soil antimony passivation rates after 35 days of cultivation at a 0.3% dosage.

[0216] The performance of the test samples obtained from the above embodiments and comparative examples was tested, and the results are summarized in the table below: Table 1. Surface composition, pore structure, and adsorption properties of the materials in the examples and comparative examples.

[0217] Table 2. Adsorption equilibrium time, cycling performance, and soil antimony passivation performance of the materials in the examples and comparative examples.

[0218] Depend on Figure 1 As can be seen, the basic iron-manganese modified chitosan composite material prepared in Comparative Example 1 exhibits a porous, irregular composite structure, with the chitosan matrix and inorganic particles jointly constituting the material surface. Figure 2 As can be seen, the material prepared in Comparative Example 1 exhibits corresponding diffraction characteristics in the common diffraction regions of ferrooxy hydroxylides and manganese oxides, indicating that a composite component containing ferrooxy hydroxylides and the first manganese oxide was formed after co-precipitation treatment. Existing X-ray diffraction results are insufficient to determine the specific crystal form of the ferrooxy hydroxylide alone, nor are they sufficient to determine the stoichiometric composition and manganese valence state of the first manganese oxide. Figure 3 The nitrogen adsorption-desorption curves and pore size distribution results shown indicate that the material prepared in Comparative Example 1 has a measurable pore structure, with a BET specific surface area of ​​110.5 m². 2 / g. Figure 4 The infrared spectrum shown retains the characteristic absorption peaks of the chitosan matrix, and exhibits changes in peak shape and intensity after co-precipitation treatment. Combined with... Figure 2 The X-ray diffraction results show that the obtained material is composed of a chitosan matrix and iron-manganese inorganic components.

[0219] Depend on Figure 5 As can be seen from the data in Table 2, the adsorption equilibrium times for Sb(III) and Sb(V) of the material prepared in Comparative Example 1 were 360 ​​min and 600 min, respectively. Figure 6 After fitting the isothermal adsorption results to the Langmuir model, the maximum adsorption capacities of the material prepared in Comparative Example 1 for Sb(III) and Sb(V) were 93.5 mg / g and 62.3 mg / g, respectively. Figure 7 (a) and Figure 7 The cyclic test results shown in (b) indicate that after five adsorption-desorption cycles, the material prepared in Comparative Example 1 retained 79.1% and 73.6% of the capacity for Sb(III) and Sb(V), respectively. These results form the basis for evaluating the effects of secondary manganese mineralization and partial cationization treatment.

[0220] Depend on Figure 8 It is evident that the content of extractable antimony in CaCl2 in the soil decreased with prolonged incubation time after the addition of the material prepared in Comparative Example 1. With increasing material dosage, the content of extractable antimony in CaCl2 further decreased after 35 days of incubation. When the material dosage was 0.3% of the soil dry weight, the passivation rate of extractable antimony in CaCl2 in the Comparative Example 1 treatment group after 35 days of incubation was 78.6%. This result serves as a basic control for evaluating the antimony passivation performance of the soil from the examples.

[0221] Depend on Figure 9As can be seen in (a)-(d), iron and manganese element signals were detected in the observation area of ​​the composite particles of the material prepared in Comparative Example 1. Figure 9 (e)-(h) show that, in Comparative Example 3, after passing through Mn 2+ After pre-adsorption and secondary manganese mineralization, the manganese element surface distribution changes compared to Comparative Example 1. Figure 9 As can be seen from (i)-(l), in the four comparative examples, partial cationization still resulted in iron and manganese elements originating from the basic iron-manganese modified chitosan complex. Figure 9 As can be seen from (m)-(p), in Example 1, both secondary manganese mineralization and partial cationization were performed simultaneously, and iron and manganese element signals were present in the observation area of ​​the composite particles. The above energy dispersive spectroscopy results show that iron and manganese components are retained in the materials obtained from different treatment routes, but this result should not be used alone as a basis for judging the chemical valence state of iron and manganese components or the chemical bonds formed with chitosan.

[0222] Depend on Figure 10 As can be seen, the materials prepared in Comparative Example 1, Comparative Example 3, and Example 1 all retain the main diffraction characteristics of the basic iron-manganese modified chitosan complex. Figure 10 As can be seen, the materials prepared in Comparative Example 1, Comparative Example 3, and Example 1 all retain the main diffraction characteristics of the basic iron-manganese modified chitosan composite. After secondary manganese mineralization, the peak intensity and shape of some diffraction peaks in Comparative Example 3 and Example 1 changed compared to Comparative Example 1, indicating that the secondary manganese mineralization treatment caused changes in the identifiable crystalline phase characteristics or relative composition of the materials. Combined with the reaction process of secondary manganese mineralization, these changes can serve as supporting evidence of changes in the manganese composition of the materials. However, existing X-ray diffraction results are insufficient to attribute the marked positions solely to the second manganese oxide, nor can they determine the stoichiometric composition, average manganese valence state, and specific crystal structure of the second manganese oxide.

[0223] Depend on Figure 11 (a) It can be seen that C, N, O, Fe and Mn element signals were detected in the materials prepared in Example 1 and Comparative Example 1. A relatively clear Cl 2p signal was also detected in Example 1. Figure 11 (b) The N 1s spectrum of Comparative Example 1 mainly includes fitting components of amino nitrogen and protonated nitrogen. Figure 11 (c) The N 1s fitting spectrum of Example 1 shows a positively charged nitrogen fitting component corresponding to the binding energy range of quaternary ammonium nitrogen, with its peak area accounting for 10.2% of the total N 1s fitting peak area. This is consistent with the process conditions of Example 1 using glycidyltrimethylammonium chloride, the thorough water washing treatment after the reaction, and the comparative example 1 without the addition of glycidyltrimethylammonium chloride. Figure 11(d) shows the Cl 2p signal change, and the result supports the introduction of a side group containing a quaternary ammonium cation in the material of Example 1. The 10.2% is the proportion of the fitted peak area of ​​quaternary ammonium nitrogen in the XPS N 1s spectrum to the fitted peak area of ​​total nitrogen, and does not represent the grafting rate of glycidyltrimethylammonium chloride or the mass fraction of quaternary ammonium nitrogen in the material.

[0224] As shown in Table 1, no independently fitted components attributable to quaternary ammonium nitrogen were detected in Comparative Examples 1 to 3 without the addition of glycidyltrimethylammonium chloride. In Examples 1 to 3, the effective components of glycidyltrimethylammonium chloride added per 1.00 g dry basis secondary manganese mineralization complex were 0.0304 g, 0.0606 g, and 0.1214 g, respectively, with corresponding XPS quaternary ammonium nitrogen fitting peak area ratios of 10.2%, 17.6%, and 28.4%. This result indicates that as the amount of effective component of glycidyltrimethylammonium chloride increases, the proportion of quaternary ammonium nitrogen fitting components detected on the material surface increases accordingly. The BET specific surface areas of Examples 1 to 3 were 105.8 m², respectively. 2 / g, 101.9 m 2 / g and 97.2 m 2 / g, lower than 110.5 m in Comparative Example 1. 2 / g indicates that while secondary manganese mineralization and partial cationization treatments increase the material composition, they also occupy some surface or pore space. The BET specific surface area of ​​Example 1 is 95.7% of that of Comparative Example 1, indicating that when 0.0304 g of glycidyltrimethylammonium chloride is added to every 1.00 g dry basis secondary manganese mineralization complex, the material retains most of its specific surface area.

[0225] Depend on Figure 12 (a) As can be seen, under the specified fixed concentration adsorption conditions, the equilibrium adsorption capacities of Sb(III) in Examples 1 to 3 were 87.8 mg / g, 92.1 mg / g, and 89.7 mg / g, respectively, all higher than the 66.8 mg / g of Comparative Example 1. Figure 12 (b) As can be seen, the equilibrium adsorption capacities of Sb(V) in Examples 1 to 3 were 82.3 mg / g, 86.7 mg / g, and 84.1 mg / g, respectively, all higher than the 52.4 mg / g in Comparative Example 1. Example 2 showed the highest equilibrium adsorption capacities for both Sb(III) and Sb(V). In Example 3, after further increasing the amount of glycidyltrimethylammonium chloride, the equilibrium adsorption capacity of Sb(V) remained at a high level, but the equilibrium adsorption capacity of Sb(III) did not continue to increase, and the BET specific surface area further decreased, indicating that there is a performance trade-off between the increase of quaternary ammonium nitrogen fitting components and the retention of pore structure.

[0226] Comparative Example 2 without Mn 2+Pre-adsorption: The basic iron-manganese modified chitosan complex was directly treated with 0.80 mmol potassium permanganate, and its equilibrium adsorption capacities for Sb(III) and Sb(V) were 71.5 mg / g and 57.6 mg / g, respectively. Comparative Example 3: The basic iron-manganese modified chitosan complex was first subjected to adsorption of Mn... 2+ Then according to the adsorption of Mn 2+ When potassium permanganate was added at 2 / 3 of its molar amount, the equilibrium adsorption capacities for Sb(III) and Sb(V) were 79.4 mg / g and 67.1 mg / g, respectively. Both equilibrium adsorption capacities in Comparative Example 3 were higher than those in Comparative Example 2, indicating that the addition of potassium permanganate before treatment with Mn... 2+ The pre-adsorption treatment on the surface of the base composite is related to the improvement of the antimony removal performance of the material.

[0227] Comparative example three samples were subjected to Mn 2+ Pre-adsorption and secondary manganese mineralization resulted in equilibrium adsorption capacities of 79.4 mg / g for Sb(III) and 67.1 mg / g for Sb(V). Comparative Example 4 underwent partial cationization, with 0.0304 g glycidyltrimethylammonium chloride active ingredient added to every 1.00 g dry-based iron-manganese modified chitosan complex; the equilibrium adsorption capacities for Sb(III) and Sb(V) were 69.8 mg / g and 63.0 mg / g, respectively. Example 1 used the same amount of glycidyltrimethylammonium chloride active ingredient and simultaneously carried out Mn... 2+ The equilibrium adsorption capacities for Sb(III) and Sb(V) after pre-adsorption, secondary manganese mineralization, and partial cationization were 87.8 mg / g and 82.3 mg / g, respectively.

[0228] Using Comparative Example 1 as the base group, Comparative Example 3 as the treatment group undergoing only secondary manganese mineralization, Comparative Example 4 as the treatment group undergoing only partial cationization, and Example 1 as the combination group undergoing both treatments simultaneously, the interaction increment was calculated by subtracting the measurements of the two individual treatment groups from the measured values ​​of the combination group and adding the measured value of the base group. The interaction increments of Sb(III) and Sb(V) equilibrium adsorption were 5.4 mg / g and 4.6 mg / g, respectively, both positive values. This result indicates that, at the current data points, the combined increment of secondary manganese mineralization and partial cationization is higher than the arithmetic sum of the increments of the two individual treatments, showing a positive interaction trend. Since the confidence intervals for the interaction increments were not listed in the current test results, these results are not considered as a conclusion of synergistic effect that has reached a statistically significant level.

[0229] Comparative Example 5 employed a method of first partially cationizing, then Mn 2+The pre-adsorption and secondary manganese mineralization treatment sequence resulted in Langmuir fitted maximum adsorption capacities of 112.0 mg / g and 83.2 mg / g for Sb(III) and Sb(V), respectively, which were lower than the 120.4 mg / g and 89.6 mg / g of Example 1. After five adsorption-desorption cycles, Comparative Example 5 showed capacity retention rates of 74.8% and 71.5% for Sb(III) and Sb(V), respectively, which were lower than the 82.3% and 78.1% of Example 1. Under corresponding conditions for other major treatments, the above results indicate that the order of secondary manganese mineralization and partial cationization affects the fitted adsorption capacity and cycle retention rate of the material. Example 1, which performed secondary manganese mineralization first and then partial cationization, achieved higher corresponding test values.

[0230] The Langmuir fitted maximum adsorption capacities for Sb(III) in Examples 1 to 3 were 120.4 mg / g, 124.2 mg / g, and 120.1 mg / g, respectively, and for Sb(V) were 89.6 mg / g, 95.1 mg / g, and 97.3 mg / g, respectively, all higher than those in Comparative Example 1. The adsorption equilibrium times for Sb(III) and Sb(V) in Example 2 were 240 min and 360 min, respectively, shorter than the 360 ​​min and 600 min of Comparative Example 1. With further increases in the amount of glycidyltrimethylammonium chloride added, the fitted maximum adsorption capacity for Sb(V) in Example 3 continued to increase, but the capacity retention rates of Sb(III) and Sb(V) after five cycles decreased to 76.2% and 72.4%, respectively. These results indicate that increasing the amount of glycidyltrimethylammonium chloride added did not lead to a simultaneous increase in all indicators; the existing data reflect the trade-off between fitted adsorption capacity, pore structure, and cycling stability.

[0231] Depend on Figure 12 (c) As can be seen, after 35 days of cultivation, the extractable antimony content in CaCl2 of the blank group, the comparative example 1 treatment group, and the example 1 treatment group were 18.60 mg / kg, 4.28 mg / kg, and 2.76 mg / kg, respectively. The 35-day soil antimony passivation rate listed in this specification is based on the extractable antimony content in CaCl2 at the beginning of cultivation (20.00 mg / kg), calculated according to the reduction ratio of extractable antimony content in CaCl2 before and after cultivation. According to this calculation method, the reduction rates of extractable antimony in CaCl2 of the blank group, the comparative example 1 treatment group, and the example 1 treatment group were 7.0%, 78.6%, and 86.2%, respectively. Under the same material dosage of 0.3%, the extractable antimony content in CaCl2 of the example 1 treatment group was lower than that of the comparative example 1 treatment group, which is consistent with the result in Table 2 that the soil antimony passivation rate of example 1 was higher than that of comparative example 1.

[0232] The foregoing description of the specifications and embodiments is intended to explain the scope of protection of this invention, but does not constitute a limitation on the scope of protection of this invention. Modifications, equivalent substitutions, or other improvements to the embodiments of this invention or a portion thereof that can be obtained by those skilled in the art through logical analysis, reasoning, or limited experimentation, based on the teachings of this invention or the foregoing embodiments, in conjunction with common knowledge, general technical knowledge, and / or existing technology, should all be included within the scope of protection of this invention.

Claims

1. A manganese-modified chitosan composite material, characterized in that, It includes a chitosan matrix, a ferrooxy hydroxyl group supported on the chitosan matrix, a first manganese oxide and a second manganese oxide, and a side group containing a quaternary ammonium cation grafted onto the chitosan matrix; The ferric oxide hydroxyl and the first manganese oxide are formed by co-precipitation of trivalent iron salt, divalent manganese salt and chitosan under alkaline conditions, and the Fe / Mn molar ratio of the trivalent iron salt to the divalent manganese salt is 3:1; The second manganese oxide is formed by reacting Mn²⁺ pre-adsorbed on the surface of a chitosan matrix containing the ferrooxy hydroxylate and the first manganese oxide with permanganate. The side group containing the quaternary ammonium cation is formed by a ring-opening reaction between the epoxy group of glycidyltrimethylammonium chloride and some of the amino groups in the chitosan matrix.

2. The iron-manganese modified chitosan composite material according to claim 1, characterized in that, The ferric oxide hydroxylate is formed by the hydrolysis and condensation of ferric salt under alkaline conditions, and the first manganese oxide is formed by the alkaline co-precipitation and aging process of divalent manganese salt.

3. The iron-manganese modified chitosan composite material according to claim 1, characterized in that, The side group of the quaternary ammonium cation is 2-hydroxy-3-trimethylammoniumpropyl, and the counter ion of the quaternary ammonium cation is chloride ion.

4. The iron-manganese modified chitosan composite material according to claim 1, characterized in that, The iron oxide hydroxylate and the first manganese oxide are formed by co-precipitation of 5.0 g chitosan with 14.61 g FeCl3·6H2O and 3.58 g MnCl2·4H2O.

5. A method for preparing the iron-manganese modified chitosan composite material according to any one of claims 1 to 4, characterized in that, Includes the following steps: S1, dissolve chitosan in hydrochloric acid solution to obtain chitosan solution; dissolve ferric salt and divalent manganese salt in water at a Fe / Mn molar ratio of 3:1 to obtain ferric-manganese salt solution; S2, the iron-manganese salt solution is added to the chitosan solution, sodium hydroxide solution is added, the pH value of the reaction system is adjusted to 8.5-9.0, a co-precipitation reaction is carried out, and after aging, solid-liquid separation, washing, drying and pulverization, the basic iron-manganese modified chitosan complex is obtained. S3, the basic iron-manganese modified chitosan complex is dispersed in an aqueous MnCl2 solution, followed by solid-liquid separation and washing, and the amount of Mn adsorbed by the basic iron-manganese modified chitosan complex is determined. 2+ Amount of substance; S4, Disperse the solid obtained in step S3 in water, add potassium permanganate, wherein the amount of potassium permanganate is equal to the amount of Mn adsorbed by the basic iron-manganese modified chitosan complex in step S3. 2+ Two-thirds of the amount of substance; during the addition of potassium permanganate, the pH value of the reaction system was maintained at 8.0±0.2 using sodium hydroxide solution. After reaction, solid-liquid separation and washing, a secondary manganese mineralization complex was obtained. S5, according to the ratio of 0.030-0.122 g glycidyltrimethylammonium chloride active ingredient added to every 1.00 g dry basis secondary manganese mineralization complex, the secondary manganese mineralization complex is dispersed in water, glycidyltrimethylammonium chloride is added, the pH value of the reaction system is adjusted to 8.3±0.2 and the reaction is carried out. After solid-liquid separation, washing and drying, the iron-manganese modified chitosan composite material is obtained.

6. The preparation method according to claim 5, characterized in that, In step S1, 5.0 g of chitosan was added to 300 mL of 0.1 mol / L hydrochloric acid solution and stirred at 30 °C and 350 r / min until dissolved; 14.61 g of FeCl3·6H2O and 3.58 g of MnCl2·4H2O were added to 300 mL of water and stirred for 30 min to obtain the iron-manganese salt solution.

7. The preparation method according to claim 5, characterized in that, In step S2, the iron-manganese salt solution is added to the chitosan solution at a rate of 5 mL / min; 1 mol / L sodium hydroxide solution is added to adjust the pH of the reaction system to 8.5-9.0, and the reaction is carried out at 45℃ and 350 r / min for 3 h. After cooling to room temperature, the mixture is aged for 12 h, the solid and liquid are separated, and the mixture is washed with water until the pH of the washing solution is 7.

0. The mixture is then vacuum dried at 60℃ for 12 h, pulverized, and passed through a 100-mesh sieve.

8. The preparation method according to claim 5, characterized in that, In step S3, 5.00 g of the basic iron-manganese modified chitosan complex is dispersed in 500 mL of Mn 2+ The pH of the reaction system was adjusted to 7.0 ± 0.2 in a 5.00 mmol / L MnCl2 aqueous solution, and the reaction was carried out at 25 °C and 300 r / min for 2 h. After contact, solid-liquid separation was performed, and the resulting solid was washed three times with water, each time using 100 mL of water. The Mn adsorbed by the basic iron-manganese modified chitosan complex 2+ The amount of substance is determined by the following formula: ; In the formula, Mn retained in the basic iron-manganese modified chitosan complex after washing 2+ Amount of substance, measured in mol; Mn in the MnCl2 aqueous solution before contact 2+ The molar concentration, expressed in mol / L; Mn in the liquid phase after contact 2+ The molar concentration, expressed in mol / L; The volume of the MnCl2 aqueous solution is expressed in liters (L). Mn washed off from the resulting solid during the washing process 2+ Amount of substance, measured in mol; The The concentration was 5.00 mmol / L. The value was 2.40 mmol / L. The value is 0.500L. The calculated value is 0.100 mmol. It was 1.20 mmol; In step S4, 0.80 mmol of potassium permanganate was added in the form of 80.0 mL of 0.010 mol / L aqueous solution over 30 min; after addition, the reaction was carried out at 25 °C and 300 r / min for 2 h.

9. The preparation method according to claim 5, characterized in that, In step S5, the secondary manganese mineralization complex is dispersed in water at a ratio of 50 mL of water per 1.00 g dry basis secondary manganese mineralization complex. The pH of the reaction system was adjusted to 8.3 ± 0.2 using a 0.1 mol / L sodium hydroxide solution. Glycidyltrimethylammonium chloride was then added, with the amount of the active ingredient being 0.030–0.122 g per 1.00 g dry basis secondary manganese mineralization complex. During the addition process, the pH of the reaction system was maintained at 8.1–8.

5. After addition, the mixture was reacted at 60℃ and 300 r / min for 15 h. The resulting solid was washed with water 5 times, each time using 20 mL of water per 1.00 g dry basis secondary manganese mineralization complex. It was then vacuum dried at 60℃ for 12 h, pulverized, and passed through a 100-mesh sieve.

10. The application of the iron-manganese modified chitosan composite material according to any one of claims 1 to 4 in the treatment of antimony-containing water bodies.